Systems and methods for separating and / or isolating nanoparticles within gaseous medium
By separating and dispersing nanofibers in a gaseous medium, forming single nanoparticles and evenly dispersing them in the fiber material, the problems of existing filters are solved, and the capture capability and life of the filter are improved.
Patent Information
- Application Number
- CN202380041770.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-08
- Filing Date
- 2023-04-07
- Publication Date
- 2025-01-07
AI Technical Summary
Existing filters are inefficient in capturing submicron particles, uneven dispersion of nanoparticles leads to a shortening of the life of the filter media, and the wet lamination method fails to successfully incorporate evenly into the nonwoven materials, affecting the filtration performance.
The nanofiber clumps are separated and isolated in a gaseous medium by a system and method, decomposed into single nanoparticles by injectors and reactors, and the nanoparticles are evenly dispersed into the fiber material through nozzles, forming a filtration with a deeper distribution medium.
It improves the filter efficiency and life of the filter, enhances the capture ability of submicron particles, extends the service life of the filter, and achieves uniform distribution of nanoparticles, improving the overall performance of the filter media.
Smart Images

Figure BDA0005143869790000391 
Figure BDA0005143869790000402 
Figure BDA0005143869790000403
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 329,158, filed April 8, 2022, the entire disclosure of which is incorporated herein by reference for all purposes. This application is also related to commonly assigned, co-pending U.S. Provisional Patent Application Serial Nos. 63 / 329,009, 63 / 328,983, 63 / 328,998, 63 / 328,970, 63 / 328,959, 63 / 329,018, 63 / 329,137, 63 / 329,146, 63 / 329,155, 63 / 329,161, and 63 / 329,162, all of which were filed on April 8, 2022, the entire disclosures of which are incorporated herein by reference in their entirety for all purposes. Technical Field
[0003] The present description generally relates to systems and methods for separating and / or isolating individual nanoparticles in a gaseous medium and producing products incorporating the individual nanoparticles within the product. Background Art
[0004] Because of their fine fiber size, fibrous materials are particularly useful for capturing contaminants in filtration devices. The fibers of filter media are measured in microns and are formed by spunbonding, meltblowing, electrospinning or other techniques. As fluid flows through the filter media, the fine fibers capture and retain contaminants within.
[0005] The two main types of filtration devices that incorporate fibrous materials include surface filters and depth filters. Surface filters (e.g., membrane layers or films) act as a barrier to capture contaminants before they enter the media structure. These surface filters typically have submicron pore sizes and narrow pore size distributions. Surface filters tend to have relatively high particle capture efficiencies. However, they also have relatively high pressure drops and low dust holding capacities. High pressure drops result in reduced air flow through the filter. Low dust holding capacities significantly reduce the life of the filter. As a result, surface filters have limited application in the air filtration industry.
[0006] Depth filters are commonly used in air filtration units with medium to high efficiency, low pressure drop, and relatively high dust holding capacity. Traditional residential and commercial air filters, such as HEPA filters, are generally rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values indicating greater efficiency in capturing specific types of particles.
[0007] Pollutants come in a wide range of sizes. However, pollutants smaller than 1 micron are the most harmful particles to the human body and are relatively difficult to filter. For example, traditional mechanical air filters typically report a MERV rating of about 8-10 for fiber filter materials. Therefore, these filter media typically do not capture submicron particles, such as viruses and other harmful pathogens.
[0008] The filtration industry has focused on two different methods of capturing these submicron particles: electrostatic forces and utilizing nanoparticles in the filter media. Electrostatic filters are formed by electrostatically charging the fibers within a fibrous material using triboelectric methods, corona discharge, hydrocharging, electrospinning, or other known methods. Electrostatic filters are most effective at capturing submicron particles, fairly effective at capturing particles between 1 and 3 microns, and least effective at capturing larger particles between 3 and 10 microns. Electrostatic fibers are commonly used in many filtration applications, such as face masks and HEPA filters, to filter submicron contaminants, such as viruses, etc.
[0009] One disadvantage of electrostatic filters is that the electrostatic charge decays over time and with filter use. As a result, the filter's efficiency decreases relatively quickly, shortening its life. For example, an electrostatic filter with an initial MERV rating of 13 may lose at least 2-3 MERV rating points after the electrostatic force decays. This compromises the integrity of the filter and may partially or completely inhibit its ability to capture submicron particles.
[0010] Another approach to capturing submicron contaminants is to use nanoparticles in combination with fibers. A filtration system may employ a filter media that includes relatively large fibers with diameters measured in microns and relatively small nanoparticles. The nanoparticles increase the surface area within the media for capturing particles by reducing the overall fiber size within the media. The nanoparticles also tend to collapse onto each other, increasing the packing density within the filter media. It has been shown that even a small number of nanometer-sized fibers in a layer formed on a microfiber material can improve the filtration characteristics of the material.
[0011] The most common method of incorporating nanoparticles into filter media is to apply a thin layer of continuous nanofibers to a non-manufactured substrate by electrospinning. The nanoparticles typically extend parallel or perpendicular to the surface of the bulk filter media layer, providing high efficiency filtration of small particles in addition to the filtration of larger particles provided by the coarse filter media. For example, U.S. Patent No. 6,743,273 discloses a filter media in which a continuous nanofiber layer is deposited on the surface of a substrate. U.S. Patent No. 10,799,820 also discloses an air filter media comprising a continuous nanofiber layer on the surface of the filter media.
[0012] While existing filter media incorporating nanoparticles have improved the relative efficiency of these filters, the commercial potential of these filters in certain applications is limited because the nanoparticles are typically dispersed on the surface of the nonwoven material. The relatively thin layer of nanoparticles on the filter surface provides only limited particle filtration and has a relatively low dust holding capacity.
[0013] Although many attempts have been made to incorporate nanomaterials into filter media to improve overall filtration efficiency, these attempts have been limited to so-called "wetlaid" methods. These wetlaid methods involve incorporating short-cut nanofibers into a liquid slurry to separate entangled nanofibers with the aid of a surfactant. For example, U.S. Patent No. 10,252,201 discloses a filter medium made of a mixture of short-cut nanofibers and short-cut coarse fibers formed by a wet-laid method. Similarly, U.S. Patent Application No. 2021 / 0023813 discloses a method for producing a composite structure consisting of a continuous fiber nonwoven substrate and discontinuous fibers (e.g., carbon nanofibers). The method includes pulling a continuous fiber nonwoven substrate through a slurry of discontinuous fibers, wherein the nanomaterial is embedded in the nonwoven substrate.
[0014] While these structures have shown improved efficiency, they also suffer from other issues such as reduced life and / or efficiency when the media is placed under normal use conditions. Additionally, these wet-laid methods have not been successful in incorporating the nanoparticles uniformly throughout the nonwoven material, which results in agglomeration of the nanoparticles within the material, further reducing its efficiency and overall dust holding capacity.
[0015] Therefore, there is a need for improved systems and methods for separating and / or isolating nanoparticles from nanofibers so that these nanoparticles can be more successfully incorporated into products (eg, filters) to improve the performance characteristics of the filters. Summary of the invention
[0016] A brief overview of the claimed subject matter is presented below to provide a basic understanding of some aspects of the claimed subject matter. This summary is not a comprehensive overview of the claimed subject matter. It is neither intended to identify the key or important elements of the claimed subject matter nor to describe the scope of the claimed subject matter. Its sole purpose is to present some concepts of the claimed subject matter in a simplified form as a prelude to the more detailed description presented later.
[0017] Provided are systems, devices and methods for separating and / or isolating single nanoparticles from nanofiber clumps, clusters or other groups in a gaseous medium. The nanofiber groups can have any suitable size and can be entangled or not entangled with each other. Single nanoparticles can be isolated in any suitable gaseous medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, water vapor, etc.) so that the nanoparticles can be dispersed into a film, layer, substrate, product or fiber stream via an airflow, aerosol, evaporator, spray or other suitable delivery mechanism. Single nanoparticles are isolated in a gaseous medium and then dispersed into a substrate or fluid stream to form a product so that the nanoparticles are more uniformly and "at a certain depth" distributed throughout the product. As used herein, the term "at a certain depth" means that the nanoparticles can be dispersed across the first surface of the substrate or other medium so that at least some of the nanoparticles are arranged between the first and second relative surfaces in the internal structure of the substrate.
[0018] In one aspect, the system comprises a housing configured to hold a nanofiber cluster, mass or other group, and a pump coupled to the housing. The system also comprises one or more channels coupled to the pump and a gaseous medium in the channel. The pump is configured to push the nanofiber group through the gaseous medium or together with the gaseous medium toward one or more surfaces in the channel at a speed and / or momentum sufficient to open and / or separate the nanofiber group into at least one single nanoparticle having a size less than 1 micron.
[0019] Applicants have discovered that individual nanoparticles can be separated from a group of nanofibers in a gaseous medium by propelling a cluster of nanofibers into a suitable surface at a velocity sufficient to generate the kinetic energy required to decompose and separate at least some of these groups of nanofibers into individual nanoparticles. In certain embodiments, the velocity of the nanoparticles is from about 500 feet per minute (fpm) to about 10,000 fpm, preferably from about 2,000 fpm to about 6,000 fpm.
[0020] In one particular aspect, the system comprises a feeder, such as a hopper or similar device, for introducing large nanofiber clusters or clumps into the system, and a separator coupled to the feeder, the feeder being configured to mechanically separate the large nanofiber clusters into smaller nanofiber groups having a size suitable for circulation in the system. The large clusters may be of any suitable size and may or may not be entangled with each other.
[0021] In an embodiment, the system further comprises a gas source, such as compressed air or other suitable gas, and a pump for sucking smaller nanofiber groups from the separator through one or more channels into the system. The compressed air source provides a motive fluid to circulate the nanofibers throughout the system and ultimately outward into a suitable dispersion device. The pump may comprise any suitable pump, such as a positive displacement pump, a centrifugal pump, an axial flow pump, etc. In one embodiment, the pump comprises an ejector configured to generate sufficient negative pressure to suck the nanofibers out of the separator and into the pump through the channel.
[0022] The system may also include an energy source, such as a second pump, a second ejector, etc., which is coupled to the first ejector and is configured to push nanofibers from the first ejector to surfaces to decompose the nanofibers and convert at least some nanofiber groups into single nanoparticles at sufficient speeds. The surface can be any surface that hinders the nanofibers from flowing through the channel, such as the inner wall of the channel at the connection point, or the inner wall of other changes in direction, such as a curved surface, a vertical surface, etc. Alternatively, the channel may include a wall or other surface that is arranged in the channel or protrudes into the channel in the fluid path. In one embodiment, the channel extends to a substantially T-shaped joint that includes two independent channels extending from the joint. The second ejector is configured to push nanofibers into the wall of the T-joint at a speed that is enough to break up at least some nanofibers.
[0023] In some embodiments, the system further comprises one or more reactors for separating individual nanoparticles that have been isolated from the nanofiber group that has not been completely decomposed. The reactor comprises a housing coupled to the channel and having an inner cavity and a negative pressure source, the negative pressure source being configured to separate the nanofiber group from the individual nanoparticles.
[0024] In embodiments, one or more reactors each comprise a substantially central rod or cylinder and one or more inlets positioned at one end of the inner chamber and substantially surrounding the central rod. The inlet is coupled to the passage so that nanofibers and single nanoparticles are sucked into the chamber through the inlet. The central rod comprises an opening at an end opposite to the inlet. The opening is coupled to the internal channel in the central rod and has an outlet coupled to a nozzle or other dispersing device. This allows nanoparticles to enter the reactor through the inlet, then enter the central rod and enter the dispersing device.
[0025] The direction of the entrance can be angled relative to the center bar so that nanofibers and nanoparticles enter the inner chamber with a lateral angle relative to the reactor outer surface. In a preferred embodiment, at least one or more entrances are directed so that when nanofibers and nanoparticles enter the reactor, they move along a direction substantially tangent to the center bar. Once they enter the annular cavity around the rod, the velocity vector (speed and direction) of nanofibers and nanoparticles produces eddy currents in the reactor, making them swirl from one end to the other around the center bar. Because single nanoparticles are obviously lighter than the entangled nanofibers that still gather together, these single nanoparticles are sucked into the entrance of the center bar. The eddy current in the chamber can also further decompose (for example, open, separate and / or individualize) nanofiber clusters when nanofiber clusters pass through the reactor.
[0026] Reactor can also comprise one or more outlets at the opposite end of inlet. Larger and heavier nanofiber clusters that have not yet decomposed are sucked out through these outlets. Therefore, isolated and individualized nanoparticles are sucked into nozzle, and nanofiber clusters are sucked out through outlet. These outlets can be coupled to the first pump or the second pump, or coupled to other pumps in the system, which are designed to further decompose the nanofiber clusters and recirculate them back in the reactor.
[0027] In an embodiment, the system may further include a dispersing device for combining a single nanoparticle with a fiber to form a product containing fibers and nanoparticles. In one embodiment, a second device comprises a nozzle or similar device for dispersing a single nanoparticle into the first stream. The system further includes a device for generating one or more fiber streams, which will be combined with a single nanoparticle stream. The fiber stream can be generated with any suitable mechanism known in the art (e.g., meltblown, spunbonded or spunlace, thermal bonding, combing, air-laid, wet-laid, co-molded, acupuncture, stitching, hydraulic entanglement, etc.).
[0028] In another embodiment, the second device comprises a nozzle for dispersing a single nanoparticle onto a first surface of a substrate comprising fibers such that the nanoparticles penetrate at least through the first surface of the substrate. The fibers can be, for example, part of a fibrous material comprising a substrate, such as a sheet, layer, film, apertured film, net, mesh, or other medium. The substrate comprises fibers and includes nanoparticles bonded to the fibers and incorporated into at least a portion of the substrate.
[0029] The nozzle is preferably configured to disperse the nanoparticles into the substrate with a certain depth. In certain embodiments, the nozzle disperses the nanoparticles throughout the substantially entire medium from the first surface to the relative second surface. In other embodiments, the nozzle disperses the nanoparticles into a part of the medium from the first surface to the position between the first surface and the second surface. In other embodiments, the nozzle disperses the nanoparticles from the first surface of the substrate to the relative second surface with a density gradient. The density of the nanoparticles can be larger at the first surface or the second surface.
[0030] The dispersing device may further include a negative pressure source or vacuum source disposed below the substrate and opposite to the nozzle to increase the penetration depth and uniformity of the nanoparticles. The negative pressure source may be any suitable suction device for sucking out the nanoparticles in the substrate, such as a suction pump.
[0031] In certain embodiments, the products are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, panel filters, etc. The nanoparticles increase the total surface area within the filter media, which increases its filtration efficiency and allows the capture of submicron pollutants without significantly compromising other factors, such as the pressure drop (i.e., air flow) through the filter. In addition, the filters produced using the systems and methods described herein are able to withstand rigorous regulation, which allows the filter to achieve the same level of filtration performance throughout its life.
[0032] In another aspect, the method for isolating a single nanoparticle in a gaseous medium includes providing a nanofiber cluster, agglomerate or other group in a gaseous medium, and pushing the nanofiber group to a surface to separate at least a portion of the nanofiber cluster into single nanofibers. The single nanoparticle can be isolated in any suitable gaseous medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, water vapor, etc.) so that the nanoparticle can be dispersed into a film, layer, substrate, product or fiber stream via an airflow, an aerosol, an evaporator, a spray or other suitable delivery mechanism.
[0033] In certain embodiments, large nanofiber clusters are first mechanically separated from one another to form smaller nanofiber clusters of a size suitable for advancement through a fiberizing device. The fiberizing device breaks down the nanofiber clusters into individual nanoparticles.
[0034] The method can also include applying negative pressure to the nanofiber clusters so that the nanofiber clusters are sucked into the compressed air stream, and the nanofiber clusters are pushed to the surface, so that at least a portion of the nanofiber clusters are decomposed into single nanoparticles. For example, the surface can be the channel inner wall of a joint, or the inner wall of other direction changes, such as a curved surface, a vertical surface, etc. In one embodiment, the nanofiber is pushed into a substantially T-shaped joint, which includes two independent channels extending from the joint. The speed of the nanofiber can be about 500 feet per minute (fpm) to about 10,000 feet per minute, preferably about 2,000fpm to about 6,000fpm.
[0035] In certain embodiments, the method also includes separating a single nanoparticle isolated from a nanofiber mass that has not yet completely decomposed. In these embodiments, particles (nanofiber mass and single nanoparticle) are entered into the inner chamber of one or more reactors. The particles are separated in the reactor so that the nanoparticles enter the nozzle, and the remaining nanofiber mass leaves the reactor and is recycled by the system. In a preferred embodiment, the particles are pushed into the reactor in a manner that is at an angle to the center bar so that the velocity vector (speed and direction) of the nanofibers and nanoparticles produces eddy currents in the reactor, making them swirl from one end to the other around the center bar. Because a single nanoparticle is obviously lighter than the entangled nanofibers that are still gathered together, these single nanoparticles are sucked into the entrance of the center bar. The eddy current in the cavity can further decompose (for example, open, separate and / or individually) the nanofiber clusters when the nanofiber clusters pass through the reactor.
[0036] In one embodiment, the first single nanofiber stream is combined with one or more fiber streams to form a fibrous material.The fiber streams may be generated by any system known in the art (eg, spunbonding, meltblowing die, carding, extrusion, etc.).
[0037] In another embodiment, single nanoparticles are dispersed on the first surface of the substrate containing fibers so that the nanoparticles at least penetrate through the first surface of the substrate. In certain embodiments, the nanoparticles are substantially dispersed throughout the entire medium from the first surface to the relative second surface. In other embodiments, the nanoparticles are dispersed by a portion of the medium from the first surface to the position between the first and second surfaces. In other embodiments, the nanoparticles are dispersed from the first surface of the substrate to the relative second surface with a density gradient. Can have a larger nanoparticle density at the first surface or the second surface.
[0038] The recitation herein of desirable objectives met by various embodiments of the specification does not imply or indicate that any or all of these objectives are present as essential features, either individually or collectively, in the most general embodiment of the specification or in any of its more specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is a side view of a fiber material having nanoparticles dispersed throughout a portion of the material;
[0040] Figure 2 is a side view of a fiber material having nanoparticles dispersed throughout the material;
[0041] Figure 3 is a side view of a fiber material having nanoparticles dispersed within the material in a gradient manner;
[0042] Figure 4 A double layer of filter media is shown;
[0043] Figures 5A-5C Biocomponent fibers incorporated into a fibrous material are shown;
[0044] Figure 6 A pleated fiber filter media is shown;
[0045] Figure 7 A representative air filter is shown;
[0046] Figure 8 A gas filter having first and second support membrane layers and a filter medium is shown;
[0047] Fig. 9A and 9B An apertured membrane used as a support membrane layer is shown;
[0048] Figures 10A-10E Various embodiments of open-pore films having nanoparticles incorporated into the film are shown;
[0049] Fig.11 A gas filter is shown;
[0050] Fig.12 A system for producing a fibrous material within a substrate is schematically shown;
[0051] Fig.13 A system for converting nanofiber clusters into individual nanoparticles is schematically shown;
[0052] Figures 14A-14C Photographs of large nanofiber clusters, small nanofiber clusters, and single nanoparticles, respectively.
[0053] Fig.15 Shows Fig.13 The system's injectors;
[0054] Fig.16 Shows Fig.13 A reactor of the system;
[0055] Fig.17 Another embodiment of a system for converting nanofiber clusters into individual nanoparticles is shown.
[0056] Fig.18 A system for producing a double-layer fiber material is shown;
[0057] Fig.19 shows a fiber material having nanoparticles dispersed within the material at a depth;
[0058] Fig. 20 A fiber material having nanoparticles dispersed within the material at a depth and a scrim layer covering the nanoparticles is shown;
[0059] Fig.21 shows a two-layer fiber material having nanoparticles dispersed on the inner surfaces of both layers; and
[0060] Fig. 22 An alternative embodiment of a system for producing a fibrous material in a fluid stream is shown;
[0061] Fig.23A is a photograph of the fiber material without the use of a binder;
[0062] Fig. 23B is a photograph of a fibrous material having a binder;
[0063] Fig.24A is a photograph of a fibrous material having nanoparticles dispersed throughout the material in the form of clumps or clusters; and
[0064] Fig. 24B is a photograph of a fibrous material having nanoparticles substantially uniformly dispersed throughout the material. DETAILED DESCRIPTION
[0065] This specification and the accompanying drawings illustrate exemplary embodiments, and should not be considered as limiting, and the claims define the scope of this specification, including equivalents. Without departing from the scope of this specification and the claims, various mechanical, composition, structural and operational changes can be made, including equivalents. In some cases, well-known structures and technologies have not yet been shown or described in detail, so as not to make the description unclear. The same numbers in two or more figures represent the same or similar elements. In addition, as long as feasible, the elements and related aspects described in detail with reference to an embodiment can be included in other embodiments that are not specifically shown or described. For example, if an element is described in detail with reference to an embodiment, and it is not described with reference to a second embodiment, the element can still be claimed to be included in the second embodiment. In addition, the description herein is for illustrative purposes only and does not necessarily reflect the actual shape, size or size of the system or the components shown.
[0066] It should be noted that, as used in this specification and the appended claims, the singular forms "a," "an," and "the," as well as any word used in the singular, include plural referents unless clearly and unambiguously limited to one referent. As used herein, the term "include" and its grammatical variations are intended to be non-limiting, such that recitation of items in a list does not exclude other like items that can be substituted or added to the listed items.
[0067] Unless otherwise indicated, any quantitative values are approximate, whether or not stated with the word "about" or "approximately." The materials, methods, and examples described herein are illustrative only and not intended to be limiting.
[0068] Provided are systems, devices and methods for separating and / or isolating single nanoparticles from nanofiber clumps, clusters or other groups in a gaseous medium. The nanofiber groups can have any suitable size and can be entangled or can be mutually unentangled. Single nanoparticles can be isolated in any suitable gaseous medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, water vapor, etc.) so that the nanoparticles can be dispersed into a film, layer, substrate, product or fiber stream via airflow, aerosol, evaporator, spray or other suitable delivery mechanisms. Isolate single nanoparticles in a gaseous medium and then disperse them into substrates or fluid streams to form products, allowing nanoparticles to be distributed more evenly and "at a certain depth" throughout the product.
[0069] As used herein, the term "to a depth" means that the nanoparticles may be dispersed across a first surface of a substrate or other medium such that at least some of the nanoparticles are disposed within the interior structure of the substrate between the first and second opposing surfaces.
[0070] As used herein, the term "nanoparticle" means any particle having a size less than 1 micron in at least one axis or dimension. For example, a fiber having a diameter or width less than 1 micron and a length greater than 1 micron is a nanoparticle as used herein.
[0071] In certain embodiments, each single nanoparticle can be a small particle, and its size range is about 1 to about 1000 nanometers, preferably about 1 to about 650 nanometers. In the number size distribution, the particle size of at least half of the particles can be measured as 100 nanometers or below. Most of the nanoparticles are usually composed of only hundreds of atoms. As the size of the nanoparticle approaches the atomic scale, the material properties change. This is due to the increase in surface area to volume ratio, causing the surface atoms of the material to dominate the material properties. Due to the very small size of the nanoparticle, compared with bulk materials (such as powders, plates, sheets or larger fibers), the surface area of the nanoparticle is very large compared to the volume ratio. This feature makes the nanoparticles have undesirable optical, physical and chemical properties, because they are small enough to limit their electronics and produce quantum effects.
[0072] In some embodiments, the nanoparticles comprise nanofibers having at least one dimension (i.e., diameter, width, height, etc., depending on the cross-sectional shape of the fiber) less than 1 micron. The nanofibers may have continuous lengths, or the nanofibers may have discrete lengths, such as 1 to 100,000 microns, preferably about 100 to 10,000 microns.
[0073] In certain embodiments, nanoparticles can be incorporated into substrates, such as nonwoven substrates comprising structures of interwoven, interlocked or bonded single fibers or lines. Nonwoven fabrics can include sheets or web structures bonded together by mechanical, thermal or chemical entanglement of fibers or filaments (and by perforated films). They can be substantially flat porous sheets, which are directly made of independent fibers or molten plastics or plastic films. The example of suitable nonwoven materials includes but is not limited to fibers, layers or webs of meltblown, spunbond or spunlace, thermal bonding, bonding combing, air-laid, wet-laid, co-molded, acupuncture, stitching, hydraulic entanglement, etc.
[0074] In certain embodiments, substrate can comprise knitting and / or woven material. Knitted material can comprise any knitting pattern suitable for desired application. Knitted material suitable for filter application comprises weft knitting, warp knitting, knitted mesh, compressed knitted mesh etc. Woven material suitable for filter application comprises textile filter media, for example monofilament fabric, multifilament fabric, nylon net, polyester net, polypropylene net etc. Woven textile can be used for for example mesh filter press cloth, woven filter pad and other die-cutting parts, centrifuge filter bag, liquid filter bag, dust collector filter bag, bed dryer filter bag, rotary drum filter, filter belt, leaf filter, roll medium etc.
[0075] In some embodiments, the fibrous material may include a structure comprising mixed or entangled chopped fibers and / or filaments. As used herein, chopped fibers refer to fibers of limited length. As used herein, filaments refer to fibers with substantially continuous length. In some embodiments, the substrate may include chopped coarse fibers, microfibers, and / or fine fibers. As used herein, "fine fibers" refer to fibers with a diameter less than 1 micron, "coarse fibers" refer to fibers with a diameter greater than 10 microns, and microfibers are synthetic fibers with a diameter less than 10 microns.
[0076] In certain embodiments, the nanoparticles are dispersed in the substrate "at a certain depth". As used herein, the term "at a certain depth" means that the nanoparticles are dispersed across the first surface of the substrate so that at least some of the nanoparticles are disposed between the first and second opposing surfaces in the internal structure of the substrate or medium. In certain embodiments, the nanoparticles are substantially dispersed throughout the entire medium from the first surface to the opposing second surface. In other embodiments, the nanoparticles are dispersed in a portion of the medium from the first surface to a position between the first and second surfaces.
[0077] In some embodiments, the nanoparticles are three-dimensionally distributed in space relative to the supporting fibers, which can increase the fiber surface area and microvolume within the fiber material. The three-dimensional distribution can also prevent complete clogging of specific portions of the fiber material, which is particularly useful in filter media because it allows fluids (e.g., air and other gases) to pass through the filter, thereby reducing the overall pressure drop across the filter.
[0078] In other embodiments, nanoparticles are arranged with density gradient across substrate thickness, so that the density of nanoparticles arranged near a surface is higher than the relative surface, or compared with the middle part of substrate, the density of nanoparticles arranged on the surface is higher. The density gradient shown can be substantially linear, it can be reduced in the form of a series of discrete steps, or the gradient can be random (that is, the reduction of density is usually not linear or step-wise). This density gradient provides many advantageous features (as described below) for some applications (such as filters).
[0079] Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic materials, acrylic, carbon, metals (e.g., alumina), polymers (e.g., nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefins, polyacetals, polyesters, cellulose ethers, polyalkylene sulfides, poly(arylene oxides), polysulfones, modified polysulfone polymers and polyvinyl alcohol, polyamides, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride, and any combination thereof.
[0080] In some embodiments, the nanoparticles can be made into bicomponent segmented cakes and islands. Then, the filaments are stretched to obtain submicron filaments. The continuous filament nanofibers are cut according to the desired length (preferably about 100 to about 10,000 microns).
[0081] In some embodiments, nanoparticles are absorbents and adsorbents. In some embodiments, nanoparticles are activated carbon fibers or activated carbon powder. In some embodiments, nanoparticles are catalytic particles or catalytic fibers. In some embodiments, nanoparticles can be obtained by feeding submicron fiber nonwovens to pulverizer or crusher or trimmer, wherein the bonded nonwoven enters, and obtains short-cut fibers. For example, low weight biocomponent melt-blown or nano melt-blown fabrics can be fed to pulverizer, and submicron nanoparticles can be obtained.
[0082] In some embodiments, different nanoparticles can be mixed. For example, nanofibers and nanobeads can be mixed. Two different nanofibers with different melting points can also be mixed so that the nanoparticles with a lower melting point can serve as a binder for the nanofibers with a higher melting point. Nanoparticles with different diameters and different lengths can also be mixed.
[0083] In some embodiments, the nanoparticles are selected from environmentally sustainable raw materials. The nanoparticles may include biosoluble glass nanofibers, biodegradable nanoparticles, compostable nanoparticles, or recyclable compositions.
[0084] Different types of nanoparticles can be combined. Some nanoparticles can be functional nanoparticles. For example, functional nanoparticles can include activated carbon and / or antibacterial materials deposited on and / or attached to the fibers in the nonwoven material. This can improve the gas absorption efficiency of the fiber and the effectiveness of killing bacteria. In addition, the nonwoven product of the microfiber nonwoven fabric deposited with glass and carbon nanoparticles will provide filtering and deodorization functions as a filter medium. In some embodiments, nanoparticles are bonded to the fibers by mechanical entanglement. This mechanical bonding can be supplemented with adhesives or bonding agents, as discussed in more detail below. In certain embodiments, nanoparticles are not curled (that is, they do not include the obvious wavy, curved, curled, coiled sawtooth or similar shapes associated with the nanoparticles in a relaxed state). In other embodiments, nanoparticles can have a coiled body structure with discrete lengths. For example, when these coiled nanofibers with discrete lengths are attached to fibers, they are entangled with each other, and are also firmly attached to the fibers, attached to the fibers and attached to the fibers around, thereby forming modified fibers. In other embodiments, attachment of the nanofibers to the microfibers is achieved by electrostatic charge attraction and / or van der Waals attraction between the fibers and the nanoparticles.
[0085] Also provided are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, plate filters, etc., which include nanoparticles dispersed in the filter media at a certain depth. In some embodiments, the filter includes one or more support layers bonded to the filter media. The support layer and / or the filter media may include nanoparticles dispersed in the layer at a certain depth. In some embodiments, a polymer layer, a membrane layer or a membrane is provided, which includes one or more holes for gas or liquid to flow through, and the nanoparticles are arranged in the polymer layer at a certain depth. In other embodiments, the fiber material includes a flexible surface layer for finger bandage pads, masks, etc.
[0086] Provided herein are systems, devices and methods for producing fibrous materials and products containing fibrous materials (e.g., gas filters). Also provided are systems and methods for isolating single nanoparticles in a gaseous medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, etc.) (rather than a liquid), and the single nanoparticles can be dispersed into another product, film, layer or substrate via an airflow, aerosol, evaporator, spray or other suitable delivery mechanism.
[0087] Although the following description is mainly directed to fiber materials and filter media, it should be understood that the devices and methods disclosed herein can be easily adapted to various other applications. For example, the fiber materials disclosed herein can be used in household cleaning products, roofing and flooring products, automotive interiors and headliners, reusable bags, wall coverings, filtration devices, insulation materials, etc. In addition, the single nanoparticles isolated and generated in the methods described herein can be used in various coatings, composite materials and / or additives, for example, polymers, food packaging, flame retardants, fuel cells, batteries, capacitors, nanoceramics, lamps, material manufacturing, production methods, reinforcements for composite materials, cements and other materials, medical diagnostic applications, medical treatment devices or therapies, tissue engineering (e.g., scaffolds for bone or tissue repair), drinking water, industrial process fluids, food and beverage products, drugs and biologics, tissue imaging, medical treatment delivery, environmental applications (e.g., biodegradable compounds), etc.
[0088] Figure 1A fibrous material or substrate 10 including a plurality of fibers 12 and nanoparticles 14 is shown. The substrate 10 has a first surface 16 and a second surface 18 opposite the first surface 16, and defines a width or thickness between the first and second surfaces 16, 18. The nanoparticles 14 have been deposited into the substrate through the first surface 16. As shown, the nanoparticles 14 penetrate through the first surface 16 into the substrate 10 at a certain "depth" between the first and second surfaces 16, 18. In some embodiments, the nanoparticles 14 penetrate from the first surface to at least 25% of the width or thickness between the first and second surfaces 16, 18, or more preferably to at least about 50% of the thickness. In other embodiments, the nanoparticles 14 substantially penetrate throughout the substrate 10 from the first surface 16 to the second surface 18.
[0089] Nanoparticles 14 preferably include individual nanoparticles (e.g., nanoparticles) that have been broken up, separated, and isolated from one another prior to being dispersed into substrate 10. Fig. 24B As shown in FIG. 1 , the nanoparticles 14 are not present in the fiber product in the form of a layer, and there are no obvious nanofiber agglomerates or bundles (such as Fig.24A This allows the nanoparticles to be more dispersed throughout the substrate, which in some applications (e.g., gas filters) provides a more effective filtration capability to filter out pollutants. In addition, this allows the nanoparticles in the fibrous material to have a greater areal density (in grams per square meter (gsm)) or "addition amount" within the material. The term "addition amount" as used herein means the areal density (gsm) of a material, fiber, or particle in a thin layer, sheet, or film of a material.
[0090] In certain embodiments, the nanoparticles may comprise about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2.0 g m 2 The specific amount of addition or surface density may depend on the application. For example, the applicant has found that a higher surface density or addition will increase the efficiency of the fiber material in filtering pollutants. Therefore, the specific amount of nanoparticles added may depend on the desired efficiency of the filter medium.
[0091] Figure 2 A fibrous material or substrate 20 is shown that includes a plurality of fibers 12 and nanoparticles 14. As shown, the nanoparticles 14 penetrate throughout the entire width of the substrate 20 from the first surface 16 to the second surface 18. In certain embodiments, the nanoparticles 14 are substantially dispersed throughout the fibers 12 of the substrate, such as Figure 2In some embodiments, the density of nanoparticles located at the first surface 16 differs from the density of nanoparticles dispersed in the central portion of the substrate 20 between the surfaces 16 and 18 by less than 50%. In some embodiments, the difference is less than 25%, preferably less than 10%. In some embodiments, the amount or number of individual nanoparticles dispersed in the central portion of the substrate 20 is at least about 50%, preferably at least about 75%, and more preferably at least about 90% of the amount of individual nanoparticles dispersed at or near the first surface 16.
[0092] In other embodiments, the nanoparticles 14 are arranged in a density gradient from the first surface 16 to the second surface 18. For example, Figure 3 A substrate 30 is shown in which the nanoparticles 14 form a density gradient, wherein the density of the nanoparticles 14 near the first surface 16 is higher than the density of the nanoparticles 14 near the second surface 18. In some embodiments, the difference between the density of the nanoparticles located at the first surface 16 and the density of the nanoparticles dispersed at the second surface 18 is greater than about 75%. In some embodiments, the difference is greater than 50%. In some embodiments, the difference is greater than 25%. In some embodiments, the amount or number of individual nanoparticles dispersed at or near the second surface 18 is less than about 50%, preferably less than about 25%, and more preferably less than about 10% of the amount of individual nanoparticles dispersed at or near the first surface 16.
[0093] Figure 3 The density gradient shown in FIG. 1 may be substantially linear from the first surface 16 to the second surface 18. Alternatively, the density of the nanoparticles 14 may decrease from the first surface 16 to the second surface 18 in a series of discrete steps, or the gradient may be random (i.e., the decrease in density is generally not linear or step-like).
[0094] In other embodiments, nanoparticles can be added to the substrate from the first and second surfaces 16, 18. In these embodiments, the area density or "addition amount" at the first and second surfaces 16, 18 can be substantially equal to each other, or they can be different depending on the application. In these embodiments, the area density or "addition amount" present in the middle of the substrate is lower than the area density or "addition amount" at the surfaces 16, 18. For example, the area density in the middle of the substrate can be about 75% of the area density of the surfaces 16, 18, or can be about 50%, 40%, or 25%.
[0095] The distribution of nanoparticles across the thickness of the fiber material can be measured, for example, using imaging techniques. An enlarged view of the fiber product is taken at a horizontal cross section in the middle of the thickness of the product using an electron microscope or other technique, which can be compared to an image taken at the upper or lower surface of the product, or all three images can be compared, to determine the extent of variation in the amount of deposited nanoparticles. Computer image analysis processing can be employed. For example, in Figure 3 In the present invention, a cross section can be taken at line AA, and a cross section can be taken at line BB. A top view of each cross section can be obtained by an electron microscope, a scanning electron microscope, and other microscopes. For example, a top view of a cross section taken at section AA can be compared with a top view taken at section BB. The number of microfibers, the number of nanoparticles, or both in samples of the same two-dimensional size can be evaluated and compared. In addition, imaging techniques can be used on three-dimensional samples. These techniques can be used to evaluate the orientation and other characteristics of the fibers. These techniques can be used to determine that the nanoparticles have been deposited into a certain depth of the substrate, have been substantially deposited across most of the substrate, substantially across the entire depth, or across a certain depth of the substrate.
[0096] The fibers of the contemplated substrate may be produced by any process including, but not limited to, air laying, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, islands in the sea staple fibers or spunbond, segmented cake staple fibers or spunbond, etc. Such processes have been described in U.S. Pat. Nos. 4,406,950, 6,338,814, 6,616,435, 6,861,142, 7,252,493, 7,300,272, 7,309,430, 7,422,071, 7,431,869, 7,504,348, 7,774,077 9,522,357, 9,993,761 and U.S. Patent Publication Nos. 2009 / 266,759, the entire disclosures of which are hereby incorporated by reference herein for all purposes.
[0097] The cross-section of the contemplated fibers may have a variety of shapes, including but not limited to round, kidney bean, dog bone, trilobal, barbell, bow tie, star, Y, etc. These shapes and / or other conventional shapes may be used with embodiments to obtain desired performance characteristics. The fibers in the substrate are held connected to each other by thermal bonds, chemical bonds, interentanglement, use of a binder (e.g., adhesive), etc.
[0098] The fibers may be man-made or natural. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfumaronitrile, polystyrene, styrene maleic anhydride, polymethylpentene, cyclic olefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (such as P(VDF-TrFE)) or terpolymers (such as P(VDF- TrFE-CFE)), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonate, acrylic acid, styrenated acrylic acid, pre-oxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic or vinyl acetate, epoxy resin, acrylic copolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof. Other conventional fiber materials are contemplated.
[0099] The fibers can include fibers of different sizes, with the diameters of the fibers typically ranging from about 1 to 1000 microns and lengths ranging from about half an inch to three inches. The fibers can be configured as a gradient density media, where the pore size decreases from the upper surface (upstream) to the lower surface (downstream) of the filter to increase capture efficiency and dust holding capacity. This configuration also allows different quantities of nanoparticles to be dispersed into the filter media at different depths. For example, the upstream side of the filter media can have the largest fiber size to allow more void space and a greater density of nanoparticles, while the downstream side of the filter media has smaller sized fibers to provide a lower density of nanoparticles. Alternatively, the structure can be reversed to provide a higher density of nanoparticles in the downstream portion of the filter media.
[0100] The fibers in the media may be held connected to other fibers by thermal bonding, chemical bonding, or entanglement. Bicomponent fibers may be used, particularly in mechanical filtration, and are formed by extruding two polymers from the same spinneret, both polymers being contained in the same filament. Suitable materials for bicomponent fibers include, but are not limited to, polypropylene (PP) / polyethylene (PE), polyethylene terephthalate (PET) / polypropylene (PP), and the like.
[0101] In some embodiments, the substrate may comprise a "high loft" nonwoven material comprising spunbond or through-air bonded carded nonwoven fibers. As used herein, the term "high loft" means that the volume of the void space is greater than the volume of the total solids. In through-air bonded carded nonwoven fibers, the loft of the substrate can be controlled in various ways known to those skilled in the art. For example, the loft can be increased by applying a small compressive force to the medium during the bonding process. In another example, the high loft nonwoven material can be produced with fibers having a larger thickness (e.g., a thickness greater than 3 denier, such as 5 denier or greater, 6 denier or greater) (discussed in more detail below). In other embodiments, the loft can be increased by using biocomponent fibers of different concentricities, such as Figure 5C shown and discussed in more detail below.
[0102] In certain embodiments, the fiber may include a silicon-based coating to improve the efficiency of the filter medium in capturing pollutants, particularly pollutants within the E2 and E3 particle groups. The silicon-based coating may include a reactive silicon coarse emulsion. Silicon emulsions may include, for example, dimethyl silicon emulsions, amino-type silicon emulsions, organofunctional silicon emulsions, resin-type silicon emulsions, film-forming silicon emulsions, and the like. In one embodiment, the reactive silicon coarse molecular emulsion comprises amino-functional polydimethylsiloxane and / or polyethylene glycol monotridecyl ether. Suitable silicon coatings are described in commonly assigned U.S. Provisional Patent Application Serial No. 63 / 406,686, filed on September 14, 2022, the full disclosure of which is incorporated herein by reference.
[0103] The filter media may contain a charge additive to modify the triboelectric charge of the fibers and increase the stability and / or duration of the triboelectric charge in the filter. This improves the overall filtration efficiency of the filter without compromising other important properties of the filter, such as life, dust holding capacity, and pressure drop or air flow through the filter. Charge additives suitable for triboelectric charging are described in commonly assigned provisional patent application serial number 63 / 410,731 filed on September 28, 2022, the entire disclosure of which is hereby incorporated by reference herein for all purposes.
[0104] Fiber can have the thickness suitable for application.In some embodiments, at least one dimension of fiber is in the range of about 1 to about 10,000 micron or about 1 to about 1,000 micron or about 10 to 100 micron.The thickness of fiber can also be measured with denier, and denier is the measurement unit of mass density of fiber linearity.In some embodiments, the linear density of fiber can be about 1 denier to about 10 denier.Nanoparticle is at least one dimension in the range of about 1 to about 1,000 nanometer or about 1 to about 100 nanometer.The size of above-mentioned fiber and nanoparticle can be diameter or width, specifically depending on the shape of fiber or nanoparticle.
[0105] For gas filters, such as pleated or non-pleated air filters, the linear density of the fibers can range from about 1 denier to about 10 denier. The filter media can contain fibers having the same or different linear densities.
[0106] The linear density of the fibers in air filters is typically about 3 deniers or less to ensure that the fibers are small enough to capture pollutants passing through the filter. Applicants have unexpectedly discovered that by using nanoparticles dispersed in the filter media, the fibers can have a greater linear density, for example, greater than 3 deniers. This is because the nanoparticles provide significant filtering capabilities. In some cases, the linear density of the fibers can be greater than 3 deniers, 5 deniers or greater, 6 deniers or greater, or as large as 7-10 deniers.
[0107] Applicants have also discovered that in some applications, fibers having a linear density greater than that used in conventional filters (e.g., greater than about 3 denier) provide more open space or pores within the filter media, which allows a greater density of nanoparticles to be dispersed therein. Although this may be counter-intuitive to one skilled in the art, Applicants have discovered that fibers having a greater linear density incorporating nanoparticles actually improve the overall efficiency of the filter.
[0108] In certain embodiments, the filter medium may include at least two different fiber thicknesses or linear densities to provide at least two different filter layers in the same filter medium. For example, in some cases, a portion of the filter medium will include fibers having a linear density greater than 3 deniers, for example, 5 deniers or greater or 6 deniers or greater. Another portion of the filter medium will contain fibers having a more standard linear density (3 deniers or less). This double-layer filter medium creates a first filter portion and a second filter portion, the first filter portion mainly using nanoparticles with a high density in fibers of greater thickness to filter pollutants; the second filter portion mainly using fibers with a lower linear density to filter pollutants, although the two portions may include nanoparticles dispersed throughout the fibers. In certain embodiments, the filter medium may include three or more separate portions or layers, each with a different range of denier fibers.
[0109] Figure 4 A dual-layer filter medium is shown, which includes a first substrate 40 having a first surface 42 and a second surface 44 opposite the first surface; and a second substrate 50 having a first surface 52 and a second surface 54 opposite the first surface. The second surface 44 of the substrate 40 is bonded to the second surface 54 of the first substrate in any manner known to those skilled in the art. The first substrate 40 contains fibers 46 having a relatively small linear density (e.g., about 3 denier or less). The second substrate 50 contains fibers 56 having a relatively large linear density (e.g., about 3 denier or greater, such as 5 denier, 6 denier or greater). The second substrate 50 also includes individual nanoparticles 58 dispersed throughout the fibers 56 and bonded to the fibers 56 and / or retained by the second substrate 50. The first substrate 40 may also include nanoparticles, or may not include nanoparticles.
[0110] The first substrate 40 is configured to filter contaminants primarily using fibers 46, although as previously described, the first substrate 40 may also include nanoparticles. The second substrate 50 is configured to filter contaminants using fibers 56 and nanoparticles 58.
[0111] In some embodiments, the substrate may contain additives, such as antimicrobial and / or antiviral compositions, such as silver, zinc, copper, silicone, tributyltin, organic compounds containing chlorine, bromine or fluorine compounds.
[0112] The fibers may include biocomponent fibers including two or more different fibers bonded to each other. The fibers may include the same material or different materials.
[0113] Figures 5A-5C Various examples of biocomponent fibers that can be used with the fiber materials disclosed herein are shown. Figure 5A A fiber 60 is shown having a core fiber 62 and a surrounding sheath fiber 64. In this embodiment, the core 62 is substantially concentric with the sheath. Figure 5B A biocomponent fiber 70 is shown having first and second fibers 72, 74 arranged side-by-side with one another. Figure 5C A biocomponent fiber 80 is shown having a core fiber 82 and a sheath fiber 84. In this embodiment, the core 82 is not concentric with respect to the longitudinal axis of the sheath 84, which increases the overall loft of the biocomponent fiber. Of course, other configurations are possible. For example, the core can include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Alternatively, the fiber can include multiple cores, or it can be divided into three, four, or more quadrants.
[0114] In certain embodiments, the fibrous material (i.e., fiber and / or nanoparticle) can be electrostatically charged so that, for example, pollutants can be captured by mechanical and electrostatic filtration. The bonding between the fiber and the nanoparticle can also be enhanced by electrostatically charging the nanoparticle, the fiber, or both. For example, in certain embodiments, the fiber is electrostatically charged so that mechanical filtration can be achieved by nanoparticles, and electrostatic filtration can be achieved by an electret substrate. Electrostatic or electret substrates can be high-loft triboelectric filtration media made by combing and acupuncture. In one of these embodiments, preferably nanoparticles are deposited in the substrate before acupuncture, and then electrostatic fibers and nanoparticles are acupunctured together.
[0115] The substrate, nanoparticles, or both may be electrostatically charged using triboelectric methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. Corona charging is suitable for charging single polymer fibers or fiber blends or fabrics. Tribocharging can be suitable for charging fibers with different electronegativity. Electrostatic fiber spinning combines the charging of polymers and the spinning of fibers into a one-step process. Charge additives suitable for tribocharging are described in commonly assigned provisional patent application serial number 63 / 410,731 filed on September 28, 2022, the entire disclosure of which is hereby incorporated by reference herein for all purposes.
[0116] Nanoparticles can be selected to have different triboelectric properties relative to the fibers to enhance particle removal using the triboelectric effect. With this approach, the resulting nanoparticles are formed in an electric field and are less susceptible to contamination by chemicals that can mitigate the triboelectric effect. Nanoparticles can also be used with different adsorption properties or surface charge characteristics than the macrofibers, such as for oil or water filtration. This difference can be used to enhance or create local electric field gradients within the filter media to enhance particle removal. The nanoparticles and macrofibers can have different wetting characteristics.
[0117] The fiber material may include a binder or bonding material, such as an adhesive or binder, to promote bonding between fibers and / or retention of nanoparticles in the matrix, so that the nanoparticles can adhere to the fibers, or otherwise be retained by the fibers within the matrix to form a stable matrix. The binder or bonding material is preferably present in a relatively small amount to bond a single nanoparticle to the fibers of the entire substrate.
[0118] The adhesive may comprise a variety of conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, polyglycolide, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs upon evaporation of the solvent.
[0119] In a preferred embodiment, the adhesive or adhesive material comprises dextrin. In yet another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In yet another embodiment, the adhesive comprises at least PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.
[0120] In some embodiments, adhesive resin is used, and adhesive resin can be cross-linked after adhesive is applied to substrate. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when solvent evaporates in adhesive formulation or heat activation in drying process. For some adhesives, crosslinking can be achieved by electromagnetic radiation (including but not limited to RF, UV or electron beam) of high energy wavelength. The amount of adhesive can be controlled by adjusting the nozzle size of sprayer 140 or the flow rate of control adhesive composition. Adhesive can be applied using nozzle, dip coating or other methods.
[0121] In some embodiments, the adhesive or adhesive material may include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate into a substrate at a certain depth. Suitable surfactants for use with the adhesive disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), etc.
[0122] In some embodiments, the substrate includes its own adhesive composition. In these embodiments, the adhesive or bonding material may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers, wherein one of the components comprises an outer sheath at least partially surrounding an inner core (see Figure 5A and 5C ).
[0123] The sheath may comprise a material that bonds to the nanoparticles. For example, the sheath may comprise a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step (as discussed below), the sheath portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously.
[0124] Fig.23A is an enlarged view of a fiber product having nanoparticles deposited therein without the use of a binder material. Fig. 23Bis an enlarged image of a fiber product in which a binder material of dextrin and water is used to adhere the nanoparticles to the fibers. As shown, with the use of a binder, the nanoparticles are more evenly adhered to the fibers.
[0125] exist Fig.23A and 23B In the example of , a substrate having bicomponent microfibers is used, the inner portion of the bicomponent microfibers being polyester and the outer portion being high density polyethylene ("HDPE"). Fig.23A A microfiber fiber product having a bicomponent microfiber substrate is shown, in which a layer of biosoluble glass nanofibers is deposited only on the surface of the substrate, relying on electrostatic forces to retain the nanofibers. Fig.23A Agglomeration of nanofibers can be seen in the substrate, and the retention of nanofibers is poor. The substrate can be produced using meltblowing, spunbonding, or other methods described herein.
[0126] exist Fig. 23B In the embodiment of, an adhesive material is used. The substrate is sprayed with a mixture of dextrin and water, and nanoparticles are applied to the substrate, wherein the uniformity of the nanofibers is higher and the retention rate is greater. In other embodiments, any adhesive material disclosed herein can be used. In addition, the nanoparticles of biosoluble glass have been deposited into a substrate at a certain depth. In this embodiment, the MERV rating of the bicomponent microfiber substrate itself is 4 to 10, which can be achieved using any method described herein. In one embodiment, due to the deposition of nanoparticles into a substrate at a certain depth and with an electrostatic charge, a microfiber substrate with an initial MERV of 8 has been used to produce a nonwoven product with a MERV of 13. In another example, a microfiber substrate with an initial MERV of 6 has been used to produce a nonwoven product with a MERV of 15. The substrate is provided on a roll, and in a roll-to-roll continuous process, as in any process and method described herein, the nonwoven product can be produced on a commercial scale. In an example, the roll-to-roll process runs at a speed of 30 feet per minute.
[0127] In certain embodiments, the fibrous materials discussed herein can be used as part of a filtration device that captures or absorbs pollutants, such as a liquid filter, a gas filter for home and commercial air filtration, a surgical mask or other face mask, etc. The filtration device can be a mechanical filter, an absorption filter, a barrier filter, an ion exchange filter, a reverse osmosis filter, a surface filter, a depth filter, etc., and can be designed to remove many different types of pollutants from air, water, or other media.
[0128] In one such embodiment, the fibrous material is incorporated into an air filter that removes particles and pollutants from the air, such as a HEPA filter (i.e., a pleated mechanical air filter), a UV line filter, an electrostatic filter, a washable filter, a media filter, a glass fiber filter, a pleated or non-pleated air filter, an activated carbon filter, a bag filter, a V-bank compact filter, a filter sheet, a flat cell filter, a filter cartridge, etc. The fibrous material can comprise the filter medium of the air filter and can be supported by a support layer, a scrim layer, or can be included in other layers or materials. Applicants have found that, as discussed herein, incorporating nanoparticles into the fibrous material significantly improves the efficiency of the air filter without compromising other factors, such as the pressure drop (i.e., air flow) through the filter. In addition, these materials increase the overall dust holding capacity, thereby extending the life of the filter, particularly compared to filters that rely only or primarily on electrostatic effects to improve efficiency.
[0129] Traditional home and commercial air filters, such as HEPA filters, are typically rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values indicating greater efficiency in capturing a particular type of particle. Traditional mechanical air filters typically report a MERV rating of about 8 for the fiber filter material.
[0130] Air filters are usually rated based on their initial efficiency (i.e., the efficiency of the air filter before use) and their efficiency over time and use. The latter efficiency is usually tested through a conditioning procedure, known as Annex J of ASHRAE Standard 52.2.
[0131] The air filters provided herein have an initial MERV rating of greater than about 10 and a pressure drop of less than about 0.5 inches of water column. In some cases, the initial MERV rating is about 11 and the pressure drop is equal to or less than about 0.17 inches of water column, or about 13 and the pressure drop is equal to or less than about 0.36 inches of water column, or about 14 and the pressure drop is equal to or less than about 0.5 inches of water column.
[0132] The gas filters provided herein have a MERV rating of 10 or higher after conditioning according to ASHRAE Standard 52.2, Appendix J. In some embodiments, the MERV rating is 13 or higher after conditioning according to ASHRAE Standard 52.2, ISO Standard 16890, or any other acceptable standard in the industry.
[0133] The MERV ratings of the fiber filter media discussed herein will vary based on many factors, including the type and size of fibers used in the filter media, the density of individual nanoparticles within the filter media, the width of the filter media, the number and size of pleats (if any), etc. MERV ratings can be measured for sheets of fiber products as well as fiber products formed into pleated filter media, and the pressure drop for each product can be different. Likewise, the pressure drop across the filter media will also depend on many factors, including those described above.
[0134] One factor that affects the MERV rating and pressure drop is the density or amount of the nanoparticles in the substrate relative to the density of the fibers in the substrate. Applicants have found that the lower the ratio between the substrate density and the nanoparticle density, the higher the MERV rating of the filter and the higher the pressure drop. In certain embodiments, the nanoparticle surface density of the filter media described herein is about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2 g / m 2 .
[0135] In some cases, the density of the nanoparticles will also depend on the density of the actual filter media (i.e., the density of the coarse fibers). As discussed in more detail below with reference to Table 2, a density ratio of about 67 (substrate gsm divided by added nanoparticle gsm) results in a pressure drop of about 0.14 inches of water column and an initial MERV rating of 10. A density ratio of about 33.4 increases the MERV rating to 10, but only results in a pressure drop of about 0.17. A density ratio of about 22.3 increases the initial MERV rating to about 12, with a pressure drop of about 0.24 inches of water column.
[0136] Thus, the efficiency or MERV rating of the filter can be increased as the amount of nanoparticles added increases. In particular, the applicant has found that, for example, an addition amount of at least 2 g / m 2 A filter with a MERV rating of approximately 10 can be achieved. 4 or 6 g / m 2 The addition of 10 g / m 2 Addition levels of 1% or more produce filters with a MERV rating of 15 or higher.
[0137] Applicants have also discovered that including fibers with greater thickness or linear density results in larger pore sizes, and therefore greater pore volumes, thereby achieving a higher density of nanoparticles within the substrate. This results in higher MERV ratings and pressure drops (as discussed below with reference to Table 2). For example, Applicants have been able to produce air filters with a MERV rating of 14 and a pressure drop of 0.5 inches of water column using 5 denier biocomponent fibers. Similarly, Applicants were able to produce filters with a MERV rating of 13 and a pressure drop of only about 0.29 inches of water column using 5 denier biocomponent fibers.
[0138] Figure 6 An example of a pleated filter media 90 is shown in FIG. Depending on the application, the filter 90 may include about 0 to 10 pleats per inch. The filter media may be mounted in a cardboard or metal frame and used as an easily replaceable filter product ( Figure 7 ). As shown, a gas filter 94 is produced using the fibrous materials described herein. As shown, the filter 94 includes a pleated fiber filter medium 96 and a support layer 98 that provides rigidity and structure to the filter medium 96.
[0139] Fig.11 A gas filter 109 produced using the fibrous material described herein is shown. The gas filter 109 includes a fibrous substrate having fibers and nanoparticles dispersed in a certain depth of the substrate. The substrate is then rolled into a cylinder, cone, or other suitable shape and can be used in applications such as gas turbine and compressor intake filters, panel filters, and the like.
[0140] Other types of filters that can be developed using the fiber materials disclosed herein include conical filter cartridges, square end cap filter cartridges, bag filters, V-bank compact filters, plate filters, flat cell filters, pleated or non-pleated bag filter cartridges, and the like.
[0141] The fiber products disclosed herein can be used in medical masks or other medical applications, such as filter cartridges in respirators. Medical masks are intended to protect medical staff and / or patients from microorganisms and other substances. For example, medical masks can block bacteria (e.g., which can be about 3 microns in size) and viruses (e.g., which can be about 0.1 microns in size). The mask is made of multiple layers of fiber material and has ear loops, laces or other structures for attaching the mask to a person's face. Metal wire can be incorporated into at least the upper portion of the mask so that at least this portion fits the person's face. The mask can include a rigid polymer structure for fixing the multiple layers of fiber material in front of the person's face. In one example, the mask has three layers. The outer layer and the inner layer contain a fiber material (e.g., spunbond polypropylene) that provides air permeability, but any material mentioned herein can also be used. The middle layer is located between the inner layer and the outer layer and includes a microfiber substrate having nanoparticles deposited into the substrate at a certain depth to provide an initial MERV greater than 8, preferably a MERV greater than 10, and more preferably a MERV of 13 or greater. The pressure drop through the mask is 3 to 6 mm of water column, and for breathability, 4 mm of water column is more preferred. The efficiency of the mask is expected to be about 95%. Other examples of masks have four or more layers. Multiple layers of fiber products can be combined into a single mask.
[0142] In certain embodiments, the nonwoven material may be included in a film or layer that includes holes, pores, or perforations. The holes may be embossed into a pattern (e.g., circles, diamonds, hexagons, rectangles, triangles, rectangles, etc.) and then stretched until holes are formed in the thinned areas produced by the embossing. Such open-cell substrates may be formed from a variety of polymers (e.g., polypropylene, polyethylene, high-density polyethylene ("HDPE"), etc.). The polymer layer may, for example, comprise an extruded film. Open-cell films are commercially available and are available as The substrate is provided in the form of a roll and the nanofibers are deposited into the substrate in a roll-to-roll process. Figures 10A-10E Examples of apertured films formed using the methods described herein are shown.
[0143] In other embodiments, the gas filter comprises a filter medium and a substantially rigid support layer bonded to the filter medium. The support layer includes fibers and individual nanoparticles dispersed within the layer at a certain depth. The nanoparticles are configured to filter pollutants passing through the support layer.
[0144] refer to Figure 8 , the composite filter member 814 includes an internal filter substrate 812 and one or more filter support members or membrane layers 810. The support member 810 can be formed by an extruded sheet of a polymer, such as a polypropylene film, a high-density polyethylene film, a polylactic acid film, or a thermoplastic polymer material, such as an extrudable fluoroplastic material, in an embodiment, a perfluoroalkoxyalkane (PFA) copolymer made from comonomers polytetrafluoroethylene and perfluoroalkyl vinyl ether. However, other polymer materials can be used, such as fluoroplastics, such as ethylene chlorotrifluoroethylene (ECTFE), ethylene tetrafluoroethylene (ETFE), or polyvinylidene fluoride (PVDF).
[0145] In certain embodiments, the support membrane layer 810 comprises individual nanoparticles dispersed at a depth within the membrane layer 810, as described above. The nanoparticles allow the support membrane layer to filter at least some contaminants that pass through the filter membrane 814, i.e., in addition to the filtration provided by the internal filter substrate 812. In other embodiments, the filter substrate 812 and / or the support membrane layer 810 include such nanoparticles.
[0146] Fluoroplastic materials such as PFA are well suited for use in filters for cleaning semiconductor components and other environments where extremely high cleanliness is required and the potential for contamination is minimized. Such support membrane layers are designed to direct fluids along their surfaces and also to direct fluids through the structure into the underlying filter substrate to remove unwanted particles from the filtrate.
[0147] like Fig. 9A and 9BAs shown, the support film layer 810 may include a plurality of holes 828. The shape of the holes is preferably circular, but it will be appreciated that other shapes are possible, such as square, rectangular, triangular, etc. The substrate may be wound into a roll, then unwound and directed through a punching machine to form the desired predetermined pattern of holes 828 in the Z direction ( Fig. 9A ). Optionally, after being set up, the sheet can be directed through a punch press in a continuous operation to form a predetermined pattern of holes 828 therein.
[0148] refer to Fig. 9B After opening the holes, the filter support member can be stretched in the machine direction, as shown by double-headed arrow 940, to elongate the holes 828 to provide a larger open area for the fluid to be filtered by the filter media or substrate 812.
[0149] In an optional embodiment, the support membrane layer 810 can be porous (i.e., not having pores 828, or in addition to having pores 828). In this embodiment, additional fluid flow can be achieved through a substantially porous support membrane layer. In an exemplary embodiment, the porosity value of the support membrane is at least 0.5 or 50%, preferably at least 0.8 or 80%, and more preferably about 0.86 or 86%. The porosity value is defined as the non-solid or pore volume fraction of the total volume of the material. A more complete description of this composite filter medium can be found in PCT Application Serial No. US2020 / 040941, the complete disclosure of which is incorporated herein by reference in its entirety for all purposes.
[0150] The support membrane layer of the present filter can be prepared by any method known to those skilled in the art. Fig. 9A and 9B In one example shown, the support film includes ribs. For example, the support film can be made by extruding a polymer material to form a sheet and then passing the sheet through a nip area provided by opposing rollers; at least one roller has an outer surface with countersunk grooves. The countersunk grooves in one roller are aligned with the outer surface or countersunk grooves of the other roller in the nip area to form a ribbed sheet having ribs upstanding from at least one surface of the sheet. Optionally, the ribs can be formed in an extrusion process or a known embossing method. Once the ribs are formed, the support film layer can be wound into a roll, subsequently unwound and directed through a punch to form a desired predetermined pattern of holes in the Z direction thereof. Optionally, after setting, the support film can be directed through a punch in a continuous operation to form a predetermined hole pattern therein, such as Fig. 9A Optionally, the support film layer can be stretched in the machine direction ( Fig. 9B ), to elongate the pores, thereby providing a larger open area for a fluid to be filtered through, for example, a filter layer or substrate. Fig.12The overall system 110 for producing the above-mentioned fibrous materials and other products is schematically depicted. As shown, the system 110 includes a feeder 120 for advancing a substrate 130 of fibrous fibers or other materials during the production process. The system 100 also includes a coater 140, a fiberizing system 150, and a heating and / or drying device 160. In certain embodiments, the system 100 also includes a vacuum or other negative pressure source 170, which is located below the substrate 130 and opposite the fiberizing system 150.
[0151] In one embodiment, the feeder 120 includes a winder 122 at the downstream end of the process and an unwinder 124 at the upstream end, which continuously winds a substrate 130 passing through the system 100. In certain embodiments, the feeder 120 may further include a support surface (not shown) extending between the winders for supporting the substrate 130 as it moves downstream through the system 100. In other embodiments, the substrate is unwound directly from the unwinder 124 to the winder 122 without another support surface.
[0152] The coater 140 is configured to spray droplets of a binder or bonding material (e.g., an adhesive or binder) onto the substrate 130 so that the nanoparticles can adhere to the fibers within the substrate 130 to form a stable matrix. The binder is preferably present in a relatively small amount to bond a single nanoparticle to the fibers throughout the substrate 130. In a preferred embodiment, the coater 140 includes a nozzle sized to generate adhesive droplets having a diameter of about 20 to 30 microns to increase the penetration depth of the adhesive through the substrate 130. Of course, the droplet size may be affected by many other parameters, including air pressure, air volume, air temperature, humidity, spray horn design, rheology / viscosity of the adhesive, carrier, etc.
[0153] Of course, it should be recognized that coating the substrate with the adhesive or bonding material can be achieved using other coating methods including ultrasonic spraying, dip coating, spin coating, gravure coating, kiss roll coating, screen coating, powder coating, electrostatic, sputtering or similar coating techniques.
[0154] As described above, the adhesive may include various conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs when the solvent evaporates.
[0155] In a preferred embodiment, the adhesive comprises dextrin. In another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In another embodiment, the adhesive comprises PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.
[0156] In some embodiments, an adhesive resin is used, and the adhesive resin can be cross-linked after the adhesive is applied to the substrate 130. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when the solvent in the adhesive formulation evaporates or thermal activation during drying. For some adhesives, crosslinking can be achieved by electromagnetic radiation of high energy wavelengths (including but not limited to RF, UV or electron beams). The amount of the adhesive can be controlled by adjusting the nozzle size of the spray coater 140 or controlling the flow rate of the adhesive composition.
[0157] In some embodiments, the adhesive can include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate into a substrate at a certain depth. Suitable surfactants for use with the adhesive disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), etc.
[0158] In some embodiments, the spray coater 140 is located upstream of the fiberizing system 150 so that the binder is sprayed before the nanoparticles are deposited. In other embodiments, the spray coater 140 is located downstream of the fiberizing system 150 so that the binder is sprayed after the nanoparticles are deposited. In other embodiments, the system 100 includes two spray coaters; one is located upstream of the fiberizing system 150, and a second spray coater (not shown) is located downstream of the fiberizing system 150 to coat the substrate 130 with a second binder after the nanoparticles are deposited.
[0159] In some embodiments, each spray coater 140 has more than one nozzle head. For example, the nozzle heads can be arranged in series to obtain better uniformity or increase the fiber spray width. Alternatively, the nozzle heads can be placed in parallel (i.e., across the width of the substrate) to ensure that the adhesive is applied over the entire width of the substrate.
[0160] In a preferred embodiment, a negative pressure source or vacuum source (not shown) is arranged below the substrate 130, opposite to the spray coater 140, to increase the penetration depth and uniformity of the adhesive. The negative pressure source can be any suitable suction device that draws the adhesive through the substrate, such as a suction pump, etc.
[0161] In some embodiments, the substrate includes its own binder composition. In these embodiments, the binder may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers 600, wherein one of the components comprises an outer sheath 64 at least partially surrounding an inner core 62. In certain embodiments, the sheath 64 and the core 62 may be substantially concentric with each other ( Figure 5A In other embodiments, the core 84 may not be concentric with the sheath 82 ( Figure 5C In other embodiments, the core 72 and the sheath 74 may be placed side by side with each other ( Figure 5B ). Of course, other configurations are possible. For example, core 184 may include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Optionally, fiber 180 may include multiple cores, or it may be divided into three, four, or more quadrants.
[0162] The sheath 64 may include a material that bonds to the nanoparticles. For example, the sheath 64 may include a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step, the sheath 64 portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously in the drying device 160.
[0163] Fig.13 Schematically depicted is a fiberizing system 150 for converting a group of nanofibers into individual nanoparticles. As used herein, the term "fiberizing" means converting (e.g., opening, separating, isolating and / or singulating) clusters, clumps, or other groups of nanoparticles that may or may not be entangled with each other into individual nanoparticles having at least one dimension less than 1 micron. Figures 14A-14C shows large clusters of entangled nanofibers ( Fig.14A ), small clusters of tangled nanofibers ( Fig. 14B ) and single nanoparticles ( Fig. 14C ) instance.
[0164] As shown, the fiberizing system 150 includes a feeder 200, such as a hopper, for feeding larger or large nanoparticle clusters / agglomerates (see Fig.14A) is introduced into the system 150. The feeder 200 may comprise any suitable hopper device known to those skilled in the art, and is preferably configured to introduce large particle clusters into the process at a specified rate, which rate depends on the fiberization rate downstream. The nanoparticles may be introduced continuously at a specified rate, or at intervals of a specific rate. The bundled large clusters of nanoparticles may be broken up before being introduced into the feeder 200.
[0165] It should be appreciated that the nanoparticles can be introduced into the fiberizing device 150 in a variety of different forms. For example, the raw nanofibers can be produced as long separate fibers. In this form, the nanofibers can be cut to obtain the desired aspect ratio.
[0166] The system 150 further includes a separator 210, such as a blender, for separating or decomposing large nanoparticle clusters / agglomerates into small nanoparticle clusters / agglomerates (see Fig. 14B ). The feeder 200 delivers the nanofibers to the separator 210 in a stable and continuous state by any mechanical means. The delivery speed will depend on various factors, such as the speed of the substrate 130 along the feeder 120, the fiberization rate of the nanoparticles, etc. By controlling the amount of nanoparticles falling into the separator 210, the amount of nanoparticles dispersed into the substrate can be controlled, thereby achieving a continuous production process.
[0167] In one embodiment, the separator 210 includes a housing 212 having a first opening 214 coupled to the feeder 200 and a second opening 216 coupled to the downstream process. The size of the second opening 216 preferably allows only nanofiber clusters of a certain size to pass through. The separator 210 may include a plurality of rotatable blades (not shown) designed to rotate around a vertical axis within the housing 212 to separate and open the coarse nanofiber clusters. The plurality of blades may have the same or different pitches and cambers to allow the entangled fibers to be sequentially decomposed or "opened" when moving from the first opening 214 to the second opening 216.
[0168] The fiberizing system 150 also includes an airflow (discussed in more detail below) that extends throughout the system from the separator 210 to the nozzle 220. The airflow (along with a series of pumps discussed below) provides the motive force that moves the nanofibers through the system 150. In one embodiment, the airflow is generated by an air compressor 230 configured to supply compressed air to the system, although it will be appreciated that other forms of gas may be used to transport the nanofibers through the system 150.
[0169] The system 150 includes one or more pumps for moving the nanofiber clusters and ultimately individual nanoparticles throughout the system. The pump may include any suitable pump, such as a positive displacement pump, a centrifugal pump, an axial flow pump, etc. In one embodiment, the first pump 240 includes a first inlet fluidically coupled to the air compressor 230 through a first channel 242 and a second inlet fluidically coupled to the separator 210 through a second channel 244. Compressed air is sucked into the first pump 240, which generates a negative pressure (e.g., a vacuum) to draw the nanofiber clusters from the separator 210 into the pump (discussed in more detail below). The system 150 may also include a second pump and a third pump 250, 260, each of which is fluidically coupled to the outlet of the first pump 240. Similarly, the second pump and the third pump 250, 260 generate a negative pressure to pull the nanofiber clusters through the third channel 252.
[0170] In certain embodiments, the pump 240 includes an ejector 300. Fig.15 As shown, the ejectors 300 each include a motive fluid inlet 302 and a nanofiber inlet 304, which are coupled to an outlet 306 via a fluid channel 308. The fluid channel 308 includes a converging inlet nozzle 310, a diffuser throat 312, and a diverging outlet diffuser 314. High-pressure, low-speed air is converted into low-pressure, high-speed air, thereby generating the pressure difference required for suction. Based on the Venturi effect and Bernoulli's principle, the primary fluid medium (e.g., compressed air) is used to generate a vacuum to draw the nanofibers into the ejector 300 and discharge them through the outlet 306. The diameter of the ejector 300 depends on the volume flow rate of the compressed air, the suction requirements, the pressure drop, and the fluid pressure of the compressed air. Review Fig.13 , the third channel 252 includes a joint 254 that divides the third channel 252 into two independent channels, each of which leads to the second pump and the third pump 250, 260. The joint 254 preferably includes a surface or wall substantially perpendicular to the third channel 252 to form a T-shaped intersection. The surface can be any surface that hinders the nanofibers from flowing through the channel, such as the inner wall of the channel at the connection point, or other inner walls with changes in direction, such as curved surfaces, vertical surfaces, etc. Optionally, the channel may include walls or other surfaces arranged in the channel or protruding into the channel in the fluid path. In one embodiment, the channel extends to a roughly T-shaped joint and includes two independent channels extending from the joint. The second ejector is configured to pull the nanofibers into the T-joint at a speed sufficient to separate at least some of the nanofibers.
[0171] As the nanofiber clusters move through the third channel 252, they are pushed against the surface or wall due to the negative pressure applied by the second and third pumps 250, 260. The velocity of the nanofibers relative to the joint 254 creates collisions with sufficient kinetic energy to cause at least some of the nanofiber clusters to break up into smaller nanofiber clusters and / or into individual nanoparticles having at least one size less than 1 micron.
[0172] To generate the kinetic energy required to break up the nanofiber clusters, air is propelled throughout the system 150 at a rate of about 500 feet per minute (fpm) to about 10,000 feet per minute, preferably about 2,000 fpm to about 6,000 fpm. The system 150 includes a sufficient amount of suction pressure, preferably at least about 20 psi. The suction pressure generates a total pressure of at least about 100 psi throughout the system.
[0173] In certain embodiments, the system 150 further includes fourth and fifth fluid channels 262, 264, which couple the outlets of the second and third pumps 250, 260 to the reactor 270. Fig.16 As shown, the reactor 270 includes a top surface 272, a bottom surface 274 and an inner annular cavity 276 extending from the top surface 272 to the bottom surface 274. The reactor 270 also includes a tube 275 in the center with an open upper inlet 278 and an outlet 280. The reactor 270 may also include one or more upper outlets 282. The reactor 270 may be coupled to an energy source (not shown) that is configured to generate a vortex of vortex gas in the annular cavity 276. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, etc. The vortex gas preferably flows from the bottom to the top of the reactor 270 around the tube 275 in the center so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 to the top surface 272.
[0174] In another embodiment, the generation of vortex does not require a separate energy source. In this embodiment, nanofiber clusters 290 and single nanoparticles 292 enter reactor 270 through bottom inlets 284, 285, 286, 287. Inlets 284, 285, 286, 287 are tilted upward to facilitate the movement of nanofibers and nanoparticles around the central tube 275. In a preferred embodiment, at least one or more of inlets 284, 285, 286, 287 are tilted so that nanofibers and nanoparticles are substantially tangent to the central tube 275 when entering reactor 270. Once they enter the annular cavity 276, the velocity vectors (speed and direction) of the nanofibers and nanoparticles generate vortices in reactor 270, causing them to swirl upward around the central tube 275 to reach the upper part of the cavity 276. The swirling gas preferably flows from the bottom to the top of the reactor 270 around the central tube 275 to move nanofiber clusters and single nanoparticles from the bottom surface 275 upward to the top surface 272. Nanofibers 290 and nanoparticles 292 are blown from the bottom of the reactor to the top without any interference. The vortex in cavity 276 can further break up (eg, open, separate and / or individualize) nanofiber clusters 290 as they pass through reactor 270.
[0175] In some embodiments, the reactor 270 may also be coupled to an energy source (not shown) configured to generate a vortex of rotating gas within the annular cavity 276. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, and the like.
[0176] The system 100 may also include another pump or negative pressure source coupled to the upper outlet 282 (e.g., see Fig.17 ). The negative pressure draws the fibers out of the outlet 282, causing the fibers 290 to leave the reactor 270. Since the individual nanoparticles 292 are significantly lighter than the tangled nanofibers 290 that are still gathered together, these individual nanoparticles 292 are sucked into the upper inlet 278 of the tube 275 in the center. At the same time, larger and heavier nanofiber clusters 290 that have not yet decomposed are drawn out from the upper outlet 284. The upper outlet 284 can be coupled to other pumps (not shown), or to the first pump 240. In this way, the nanofiber clusters 290 are further decomposed through the process again, thereby forming a re-feed system to further decompose the remaining nanofiber clusters.
[0177] The outlet 280 of the central tube 275 is connected to the nozzle 220 (see Fig.13 ) coupling. Individual nanoparticles 292 are drawn into nozzle 220, where they are dispersed onto the substrate surface or into the fiber stream (discussed below). Nozzle 220 may comprise any suitable nozzle known to those skilled in the art. In one embodiment, nozzle 220 has a plurality of outlets, the outer dimensions of which are tailored according to the size (i.e., area) of the substrate passing under nozzle 220. Nozzle 220 will disperse the nanoparticles onto the substrate at a rate driven by the pressure of the entire system.
[0178] In certain embodiments, system 100 includes more than one nozzle coupled to outlet 280 of reactor 270. The nozzles can be arranged on the substrate in any suitable arrangement (eg, side-by-side, in series, in parallel, etc.).
[0179] It will be appreciated that pump 240 or pumps 250, 260 can feed the nanofiber / air mixture stream directly into nozzle 220 (i.e., bypassing reactor 270). In this embodiment, the pressure within the system is designed to generate sufficient kinetic energy to break up or open up substantially all of the nanofibers into individual nanoparticles, thereby eliminating the need for reactor 270 to separate the nanoparticles from larger fiber clusters.
[0180] Reference Fig.17, another embodiment of a fiberizing system 320 will now be described. As shown, the fiberizing system 320 includes a separator 325 for separating larger or large nanofiber clusters passing through the system 320 into smaller nanofiber clusters. A first ejector 326 is coupled to the outlet of the separator 325 for pulling the nanofibers from the separator 325 into the system 320. An air compressor (not shown) is also coupled to the ejector 326 to provide a motive fluid, as described above.
[0181] Similar to the previous embodiments, the second and third ejectors 330, 340 are coupled to the outlet of the first ejector 326. The nanofibers are drawn from the first ejector 320 and are pushed toward the surface of the T-junction 350 to break up at least some of the nanofibers into smaller clusters or individual nanoparticles.
[0182] Each of the second and third ejectors 330, 340 has an outlet coupled to another T-junction 360, 370. As before, the nanofibers are pushed toward the surface of the T-junction 360, 370 to further decompose them. The T-junction 360, 370 are each coupled to two fluid channels entering the bottom 380 of the reactor. Therefore, the bottom 380 of the reactor has four separate inlets 382, 384, 386, 388 for the passage of nanofibers. Each of these inlets is preferably tilted upward and located at opposite corners of the reactor. This allows the nanofibers to enter the vortex of the reactor and then swirl upward to the upper part 390 of the reactor.
[0183] As previously referenced Fig.16 The reactor comprises an annular chamber, wherein the tube at the center has an open upper end and a lower end coupled to a nozzle. The nanofibers that have been fully decomposed into individual nanoparticles flow through the open upper end and enter the tube at the center for dispersion through the nozzle. The heavier nanoparticle clusters that have not yet decomposed leave the reactor through one of four independent outlets 392, 394, 396, 398. Ejectors 410, 420 provide the power to extract the nanofibers from the reactor 400, as described above. Outlets 392, 394 are each coupled to ejector 410 by a T-shaped intersection 412, and outlets 396, 398 are each coupled to ejector 420 by a T-shaped intersection 422. In this case, the nanofibers flow into one channel from two channels when passing through intersections 412, 422.
[0184] The ejectors 410, 420 are each coupled to the T-intersections 430, 440. As previously described, the nanofibers are pushed into the T-intersections 430, 440 to further break them up into individual nanoparticles. Then, the T-intersections 430, 440 are each coupled to the bottom 380 of the reactor 400 (via inlets 432, 434, 442, 444). This allows the nanofibers to be returned to the reactor 400 for further processing. This process is continued for each nanofiber cluster until it is completely broken down into nanoparticles and enters the nozzle through the tube in the center. As a final step, the individualized nanofibers are sprayed from the nozzle with air onto any substrate or mixed with any fiber spinning stream. In this process, the suction is up to 20psi and the pressure is up to 100psi.
[0185] In certain embodiments, fibrosis system 150 may include a separate control system that monitors nanofibers to determine when they are broken down into individual nanoparticles suitable for passing through nozzles. The control system may, for example, simply monitor the pressure of the entire system to ensure that enough pressure is applied to the nanofibers to break them down into nanoparticles. Alternatively, the control system may include various sensors arranged by the system to detect the characteristics of nanoparticles, such as weight or size. The sensor may be arranged in, for example, reactor 400 so that the control system may control the various parameters of reactor 400, such as the negative pressure applied to outlet 392,394,396,398, the speed of the eddy current of the annular chamber, or the pressure applied to the tube at the center that nanoparticles are sucked into the nozzle.
[0186] Fig.18 Another embodiment of a system 500 for producing a multilayer nonwoven material is shown. As shown, the system 500 includes a first unwinder and a second unwinder 502, 504 and a single winder 506 for winding a first substrate and a second substrate 510, 512 downstream of the system 500. As in the previous embodiment, the system 500 may also include a support surface (not shown) for each substrate 510, 512. The first unwinder and the second unwinder 502, 504 are used to advance the first substrate and the second substrate 510, 512 into the process, where they are connected together and then wound onto the single winder 506, as described below.
[0187] The system 500 includes first and second spray coaters 520, 522, each located downstream of the first and second unwinders 502, 504, for applying adhesive to the first and second substrates 510, 512. The system 500 also includes first and second fiberizing systems / devices 530, 532, which are located downstream of each spray gun 520, 522. As previously discussed, the fiberizing devices 530, 532 generate individual nanoparticles and disperse the nanoparticles onto the substrates 510, 512.
[0188] After the nanoparticles are dispersed into the substrates 510, 512, the two substrates are connected together at the connection point 540 so that they are advanced downstream together. The two substrates may be bonded to each other at this point, or they may simply be placed one on top of the other.
[0189] The system 500 also includes a heater / drying device, such as an IR oven 550, located downstream of the connection point 540 of the two substrates. The heating / drying device heats and dries the two substrates to bond them to each other and to bond the nanoparticles to the fibers within the substrates. The substrates can, for example, be laminated to each other.
[0190] In certain embodiments, nanoparticles are dispersed into substrates 510, 512. In such an embodiment, system 500 is designed so that nanoparticles are dispersed by the first surface of each substrate. Then, substrates can be connected together so that the first surface faces each other. Alternatively, the first surface can be opposite to each other (that is, substrate is connected at the second relative surface of each substrate). In another embodiment again, the first surface of the first substrate is connected to the second surface of the second substrate.
[0191] Fig.19 A filter product 700 is shown, comprising a filter medium 710 of a nonwoven material, comprising fibers 722 and nanoparticles 720 dispersed in at least a portion of the filter medium 710. As shown, the filter medium 710 has a first upper surface 712 and a second lower surface 714. The nanoparticles have been dispersed through the upper surface 712 so that they extend beyond the upper surface 712 and into the filter medium 710 to a certain depth, as described above. The filter product 700 further includes a support layer 730, which can be any suitable support layer known in the art, such as a substantially rigid polymer that provides support for the filter medium 710, or an open membrane having a plurality of pores for gas or fluid to pass through (as described above).
[0192] Fig. 20Another filtration product 740 is shown that includes a filter media 710 of fibrous material including fibers 722 and nanoparticles 720 dispersed in a portion of the filter media 710. In this embodiment, the product 740 includes a scrim layer 750 bonded to a support layer 730.
[0193] Fig.21 A dual layer filtration product 760 is shown, which includes first and second filter media 762, 764 bonded to each other. As shown, nanoparticles 720 have been dispersed in a certain depth of each filter medium 762, 764. In this embodiment, the nanoparticles 720 have been dispersed through the inner surface 766, 768 of the filter media 762, 764. In another embodiment (not shown), the nanoparticles are dispersed through the outer surface 770, 772 of the filter media 762, 764. In yet another embodiment, the nanoparticles 720 can be deposited on the inner surface 766 of the medium 762 and the outer surface 772 of the medium 764.
[0194] In yet another aspect, the system for producing fibrous material comprises a first device for generating one or more fiber streams and a second device for isolating nanoparticles in a gaseous medium. The second device is dispersed into the nanoparticles in the stream and the stream is fed into the fiber stream to form the fibrous material. The system may also include a dispersing device, for example a nozzle, which is coupled to the second device and is configured to feed the nanoparticles substantially uniformly into the fiber stream. The fiber stream can be generated with any suitable mechanism known in the art (for example meltblowing, spunbonding or spunlace, thermal bonding, combing, air-laid, wet-laid, extruding, co-molding, acupuncture, stitching, hydraulic entanglement, etc.).
[0195] In one example, the system can include a spunbond line, in which filaments are formed by spinning molten polymer and stretching the molten filaments. The fiber bundles of the filaments are separated and spread, and then layered on a net to form a web. The fibers are bonded in the form of sheets by thermal bonding and embossing. The first stream 630 can be introduced, for example, before the attenuation zone or before the bonding (consolidation) process.
[0196] In another embodiment, the system can include two carding machines arranged in series with each other. The first stream 630 can be introduced at any point after the first carding line and before the second carding line, so that the nanoparticles are sandwiched between the two carded fiber webs. Afterwards, all fibers (including the nanoparticles) are bonded together in a hot air bonding oven (the nanoparticles are thermally interlocked).
[0197] Fig. 22Another embodiment for generating one or more fiber streams is shown. In this embodiment, the nanoparticles are dispersed between two meltblowing dies where the molten polymer is pushed through small holes to form fibers. When the nanoparticles meet the fibers while they are still tacky, they mechanically entangle with the fibers and thermally bond to the fibers. Thus, in some embodiments, no additional bonding process is required. Fig. 22 As shown, the apparatus 600 for forming a fiber structure includes a fiberizing system 610 similar to one of the above-described systems and devices. The fiberizing system 610 includes a nozzle 620 or similar device for dispersing individual nanoparticles into a first stream 630. The apparatus 600 further includes a system for generating one or more fiber streams that will be combined with the single nanoparticle stream 630. The system may include any system known in the art, such as spunbonding, carding, extrusion, etc.
[0198] In another embodiment, the device comprises a first and a second feeder, such as a hopper 640, 642, which is coupled to the first and second extruders 650, 652. For example, each extruder can include an extrusion screw (not shown) driven by a conventional drive motor (not shown). When the polymer is advanced through the extruders 650, 652, the polymer is gradually heated to a molten state due to the drive motor rotating the extrusion screw. Thermoplastic polymers are heated to a molten state and can be completed in multiple discrete steps, when they advance to two melt-blown dies 660, 662 through the discrete heating zones of the extruders 650, 652, respectively, their temperature gradually increases. Melt-blown dies 660, 662 can be another heating zone, wherein the temperature of the thermoplastic resin is maintained at a higher level to extrude.
[0199] Each meltblowing die 660, 662 is configured so that the two attenuating air streams of each die converge to form a single air stream that entrains and attenuates the molten strands as they flow out of the small holes or orifices 672 in the meltblowing die. The molten strands 20 are attenuated into fibers or, depending on the degree of attenuation, into microfibers, which have a relatively small diameter, typically smaller than the diameter of the orifices 672. Thus, each meltblowing die 660, 662 has a corresponding single primary air stream 680, 690 containing entrained and attenuated polymer fibers.
[0200] The primary air streams 680, 690 containing polymer fibers are aligned to converge at the forming zone 700. In addition, a first stream 630 of individual nanoparticles is added to the two primary air streams 680, 690 of thermoplastic polymer fibers or microfibers at the forming zone 30. The introduction of the individual nanoparticles into the two primary air streams 680, 690 of fibers is intended to produce a distribution of secondary fibrous material 32 in the combined primary air streams 680, 690 of fibers. This can be achieved by merging the first stream 630 of individual nanofibers between the two primary air streams 680, 690 so that all three air streams converge in a controlled manner.
[0201] Examples of suitable meltblowing dies that can be used to produce nonwoven materials are discussed in more detail in U.S. Patent Nos. 6,972,104, 8017534, and 7772456, and U.S. Patent Application No. US20200216979A1, the complete disclosures of which are incorporated herein by reference in their entirety for all purposes.
[0202] Example 1
[0203] A microfiber substrate of bicomponent fibers is provided in the form of a roll, having an inner circular portion of polyester and an outer concentric portion of HDPE. In a roll-to-roll process, the substrate is sprayed with an adhesive and nanofibers or nanoparticles of biosoluble glass fibers are deposited. The nonwoven product is then placed in an oven for heating, and the cooled nonwoven product is collected on another roll. According to the following Figure 12-16 The nanoparticles were deposited by the process described in . In the experiments, biosoluble glass nanofibers were used. The nanofibers had a diameter of about 700 nanometers and a length of about 500 micrometers. In the following examples, a carded hot air bonded nonwoven made of bicomponent fibers was used as the substrate:
[0204] Flat sheet filter media samples were tested at a filtration velocity of 110 fpm. Sample size was 12" x 12". NaCl salt particles ranging from 0.3 to 10 microns were used as the contaminant.
[0205] Example 2
[0206] A carded nonwoven made of 3-denier PET / PE bicomponent fibers was used as a substrate. A composition comprising water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide was used as a binder. Different nanofiber addition amounts were controlled by adjusting the line speed.
[0207] Table 1
[0208]
[0209]
[0210] This example shows that by controlling the amount of nanoparticles added, the MERV rating can be increased from MERV 7 to MERV 13.
[0211] Example 3
[0212] A high loft hot air bonded carded nonwoven with 5 denier bicomponent fibers was used as the substrate. A typical starch adhesive was diluted and sprayed before nanofiber deposition. As the solvent evaporated and dried under an IR heater, the starch fully bonded the nanofibers.
[0213] Table 2
[0214]
[0215] Example 4
[0216] Use spunbond or meltblown media as a substrate, wherein nanoparticles are incorporated into the substrate after IPA discharge, as described herein. Spunbond fibers are made of a molten polymer that is spun and stretched to produce filaments. The average basis weight of the substrate is about 90gsm, and the average thickness is about 0.57mm. Use a base sample without any nanoparticles incorporated. Prepare 4 separate samples, which include nanoparticles incorporated into the substrate, as described herein. In sample 2, nanoparticles are incorporated into meltblown fibers after IPA discharge. In samples 1, 3, and 4, nanoparticles are incorporated into spunbond fibers after IPA discharge. The test results are shown in Table 3 below.
[0217] Table 3
[0218]
[0219]
[0220] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was higher than that of the base samples, and the efficiency of the E2 and E3 particle groups was significantly improved. The overall MERV rating of the samples increased from MERV 7 (base sample) to MERV 12 to MERV 16 (using nanoparticles). The pressure drop of the base sample without nanoparticles was 0.07 inches of water column. The pressure drop of samples 1-4 increased slightly, ranging from 0.17 to 0.41 inches of water column. In sample 2, where nanoparticles were incorporated into meltblown fibers, the MERV rating was 14 and the pressure drop was 0.24 inches of water column.
[0221] Example 5
[0222] 5 denier hot through bonded carded fibers were used as the substrate. A base sample without nanoparticles incorporated was used. Two separate samples were prepared that included nanoparticles incorporated into the substrate as described herein. The test results are shown in Table 4 below.
[0223] Table 4
[0224] sample# Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.31 57% 90% 98% 13 2 5D carded fiber 0.33 61% 92% 98% 13
[0225] As shown, the efficiency of the filter media samples incorporating nanoparticles increased significantly over the base samples in all three particle groups. The overall MERV rating of the samples increased from MERV 6 (base sample) to MERV 13 (with nanoparticles). The pressure drop of the base sample without nanoparticles was 0.03 inches of water column. The pressure drop of samples 1 and 2 increased slightly, ranging from 0.31 to 0.33 inches of water column.
[0226] Example 6
[0227] Meltblown fibers were used as substrates. The average basis weight of the substrate was about 24 gsm and the average thickness was about 0.4 mm. A base sample without nanoparticles or adhesives (e.g., PVOH) was used. Sample 1 included meltblown fibers with the tape side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 2 included meltblown fibers with the velvet side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 3 included meltblown fibers with PVOH sprayed thereon, and nanoparticles were incorporated into the fibers, as described herein. The test results are shown in Table 5 below.
[0228] Table 5
[0229]
[0230]
[0231] As shown, in all three particle groups, especially in the E1 particle group, the efficiency of sample 3 incorporating nanoparticles increased compared to the other three base samples. The overall MERV rating of sample 3 increased from MERV 13 or 14 (base samples) to MERV 15 (using nanoparticles). The PVOH added to samples 2 and 3 did not significantly increase the pressure drop (i.e., 0.35 for the base sample, 0.38 and 0.41 for samples 1 and 2). The pressure drop of sample 3 did increase from about 0.40 inches of water column to about 1 inch of water column. In sample 3, incorporating nanoparticles into the meltblown fiber, the MERV rating was 15 and the pressure drop was 1.02 inches of water column.
[0232] Example 7
[0233] 5 denier hot through bonded carded fibers were used as the substrate. A base sample without nanoparticles was used. Seven additional samples were prepared, which included 5 denier carded fibers with nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 6 below.
[0234] Table 6
[0235] sample# Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.07 7% 31% 69% 7 2 5D carded fiber 0.09 5% 36% 69% 7 3 5D carded fiber 0.15 16% 51% 77% 9 4 5D carded fiber 0.16 21% 58% 81% 10 5 5D carded fiber 0.17 31% 70% 90% 11 6 5D carded fiber 0.28 46% 85% 96% 12 7 5D carded fiber 0.32 58% 91% 97% 13
[0236] As shown, the seven samples incorporating nanoparticles had higher efficiencies than the base samples in all three particle groups, especially in the E2 and E3 particle groups. The overall MERV rating increased from MERV 6 (base sample) to MERV 7 to MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.32 inches of water column.
[0237] Example 8
[0238] High loft spunbond fibers were used as substrates in continuous fiber production lines. This test included two different versions: 205-6 and 205-2, in which the settings on the continuous fiber production line were changed to produce two substrates with different weights and thicknesses. Each version (205-6 and 205-2) used a base sample without nanoparticles incorporated. Six additional samples were prepared, which included 205-6 and 205-2 fibers and nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 7 below.
[0239] Table 7
[0240] sample# Substrate PD E1 E2 E3 MERV Base 205-6 0.04 0% 9% 43% 6 Base 205-2 0.04 0% 8% 37% 6 1 205-6 0.86 88% 98% 99% 15 2 205-2 0.48 79% 96% 99% 14 3 205-6 0.87 82% 97% 99% 14 4 205-2 0.42 61% 90% 98% 13 5 205-6 0.78 79% 97% 99% 14 6 205-2 0.23 44% 79% 96% 11
[0241] As shown, in all three particle groups, the six samples incorporating nanoparticles showed significant improvements in efficiency over the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 11 to MERV 14 (with nanoparticles). The pressure drop only increased from 0.04 inches of water column to a maximum of 0.87 inches of water column. The pressure drop in the 205-2 sample only increased to a maximum of 0.48 inches of water column.
[0242] Example 9
[0243] Spunbond and meltblown fibers were used as substrates. For spunbond fibers, the average basis weight of the substrate was about 70 gsm, while for meltblown fibers, the average basis weight of the substrate was about 24 gsm. The average thickness of the substrate was about 0.75 mm. A base sample without nanoparticles was used. Five additional samples were prepared, including spunbond and meltblown fibers and nanoparticles incorporated into the fibers, as described herein. In samples 1-3, nanoparticles were sprayed onto meltblown fibers. In samples 4 and 5, nanoparticles were sprayed onto spunbond fibers. In addition, in samples 1 and 2, the adhesive PVOH was not sprayed onto the substrate. PVOH was sprayed onto samples 3-5. The test results are shown in Table 8 below.
[0244] Table 8
[0245] sample# Substrate PD E1 E2 E3 MERV Base Spunbond+MB 0.07 2% 17% 29% 5 1 Spunbond+MB 0.41 100% 100% 100% 16 2 Spunbond+MB 0.56 100% 100% 100% 16 3 Spunbond+MB 0.26 99% 100% 100% 16 4 Spunbond+MB 0.4 100% 100% 100% 16 5 Spunbond+MB 0.17 97% 100% 100% 16
[0246] As shown, in all three particle groups, the five samples incorporating nanoparticles showed a significant improvement in efficiency over the base samples. The overall MERV rating increased from MERV 5 (base sample) to MERV 16 (with nanoparticles). The pressure drop only increased from 0.07 inches of water column to a maximum of 0.56 inches of water column. In samples 3-5 (PVOH sprayed onto the substrate), the pressure drop only increased to a maximum of 0.4 inches of water column.
[0247] Example 10
[0248] 5 denier hot air bonded carded glass fiber was used as the substrate. A base sample without nanoparticles was used. Three additional samples were prepared, which included 5 denier carded glass fibers and nanoparticles incorporated therein. The test results are shown in Table 9 below.
[0249] Table 9
[0250] sample# Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.27 59% 91% 99% 13 2 5D carded fiber 0.18 45% 83% 98% 12 3 5D carded fiber 0.24 54% 89% 99% 13
[0251] As shown, in all three particle groups, the three samples incorporating nanoparticles showed a significant improvement in efficiency over the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 12 or MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.27 inches of water column.
[0252] Embodiment 11
[0253] A fiber mixture of 5 denier and 7 denier hot air bonded combed glass fibers was used as the substrate. The medium was hot air bonded. A base sample without nanoparticles was used. Nineteen additional samples were prepared, which included a fiber mixture of 5 denier and 7 denier combed glass fibers and nanoparticles incorporated therein. The test results are shown in Table 10 below.
[0254] Table 10
[0255]
[0256]
[0257] As shown, in all three particle groups, all 19 samples incorporating nanoparticles showed significant improvements in efficiency over the base samples. The overall MERV rating increased from MERV 6 (baseline samples) to MERV 10 to MERV 13 (using nanoparticles) (most samples were rated MERV 13). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.31 inches of water column.
[0258] Although these devices, systems and methods have been described in detail herein according to certain preferred embodiments, many modifications and changes may be made thereto by those skilled in the art. Therefore, the foregoing description should not be interpreted as being limited thereto, but rather should be interpreted as including the aforementioned obvious changes, and only limited by the spirit and scope of the following claims.
[0259] For example, in one aspect, a first embodiment is a method for separating or isolating individual nanoparticles in a gaseous medium. The method includes providing a nanofiber group in a gaseous medium and pushing the nanofiber group toward a surface to separate at least a portion of the nanofiber group into individual nanoparticles, wherein at least one dimension of the individual nanoparticles is less than 1 micron.
[0260] A second embodiment is the first embodiment wherein the group of nanofibers is pushed to the surface at a speed of about 500 feet per minute (fpm) to about 10,000 fpm.
[0261] A third embodiment is the second embodiment wherein the velocity is from about 2,000 fpm to about 6,000 fpm.
[0262] A fourth embodiment is any combination of the first three embodiments, wherein the gaseous medium is compressed air.
[0263] A fifth embodiment is any combination of the first four embodiments, further comprising mechanically separating the large nanoparticle clusters into nanofiber groups.
[0264] The sixth embodiment is any combination of the first five embodiments, further comprising applying negative pressure to the nanofiber group to draw the nanofibers into the air flow.
[0265] The seventh embodiment is any combination of the first six embodiments, further comprising applying negative pressure to the air flow to push the nanofiber group toward the surface.
[0266] An eighth embodiment is any combination of the preceding seven embodiments, further comprising pushing the nanofiber through the channel into the joint, wherein the surface is located at the joint.
[0267] A ninth embodiment is any combination of the first eight embodiments, wherein the joint is a substantially T-shaped joint.
[0268] The tenth embodiment is any combination of the first nine embodiments, further comprising:
[0269] pushing the single nanoparticles and the nanofiber groups into the inner cavity of the reactor; and separating the nanofiber groups from the single nanoparticles within the reactor.
[0270] An eleventh embodiment is any combination of the preceding ten embodiments, wherein the individual nanoparticles and nanofiber groups are propelled into the lumen at a velocity vector that creates a vortex within the reactor.
[0271] A twelfth embodiment is any combination of the preceding eleven embodiments, wherein the lumen comprises a substantially central tube and the velocity vector comprises a direction transverse to the longitudinal axis of the tube.
[0272] A 13th embodiment is any combination of the first 12 embodiments, wherein the direction is substantially tangential to the outer surface of the tube.
[0273] A fourteenth embodiment is any combination of the previous thirteen embodiments, wherein the central tube comprises a substantially cylindrical outer surface with an upper opening, wherein the individual nanoparticles and nanofiber groups are propelled in a vortex around the outer surface of the central tube.
[0274] A 15th embodiment is any combination of the previous 14 embodiments, wherein a single nanoparticle is sucked into the upper opening of the central tube.
[0275] A sixteenth embodiment is any combination of the preceding fifteen embodiments, further comprising applying negative pressure to the cavity to aspirate the nanofiber group from the cavity.
[0276] A seventeenth embodiment is any combination of the previous sixteen embodiments, wherein the nanofiber population comprises entangled chopped nanoparticles.
[0277] The 18th embodiment is any combination of the previous 17 embodiments, and further includes applying negative pressure with an ejector.
[0278] A nineteenth embodiment is any combination of the previous eighteen embodiments, further comprising feeding large nanoparticle clusters to the separator at a specified rate.
[0279] A twentieth embodiment is any combination of the preceding nineteen embodiments, further comprising drawing individual nanoparticles from a centrally located tube of the lumen into a nozzle and dispersing the individual nanoparticles into fibers to form a product.
[0280] A 21st embodiment is any combination of the previous 20 embodiments, wherein the product is a filter.
[0281] In a second aspect, a first embodiment is a system for separating or isolating single nanoparticles in a gaseous medium. The system comprises a housing configured to contain a group of nanofibers, a pump coupled to the housing, and a channel coupled to the pump and having a surface, wherein the pump is configured to push the group of nanofibers into the surface at a speed sufficient to generate single nanoparticles from at least a portion of the group of nanofibers.
[0282] A second embodiment is the first embodiment wherein the velocity is from about 500 feet per minute (fpm) to about 10,000 fpm.
[0283] A third embodiment is the second embodiment wherein the velocity is from about 2,000 fpm to about 6,000 fpm.
[0284] A fourth embodiment is any combination of the previous three embodiments, wherein the set of nanoparticles comprises entangled chopped nanoparticles.
[0285] A fifth embodiment is any combination of the first four embodiments, wherein the channel comprises a joint and the surface is located at the joint.
[0286] A sixth embodiment is any combination of the first five embodiments, wherein the joint is a substantially T-shaped joint.
[0287] A seventh embodiment is any combination of the first six embodiments, further comprising a compressed air source and a second passage coupling the compressed air source to the pump.
[0288] An eighth embodiment is any combination of the preceding seven embodiments, wherein the pump comprises an ejector configured to generate negative pressure to draw the nanofiber group out of the housing and through the first channel.
[0289] A ninth embodiment is any combination of the previous eight embodiments, further comprising a reactor having an inner cavity coupled to the channel, wherein the reactor is configured to separate the nanofiber groups from the individual nanoparticles.
[0290] The tenth embodiment is any combination of the first nine embodiments, wherein the inner cavity of the reactor comprises one or more inlets coupled to the channel, and wherein the pump is configured to propel the individual nanoparticles and nanofibers through the inlet with a velocity vector that creates a vortex within the reactor.
[0291] An eleventh embodiment is any combination of the preceding ten embodiments, wherein the lumen comprises a substantially central tube and the velocity vector comprises a direction transverse to the longitudinal axis of the tube.
[0292] A twelfth embodiment is any combination of the previous eleven embodiments, wherein the direction is substantially tangential to the outer surface of the tube.
[0293] A 13th embodiment is any combination of the previous 12 embodiments, wherein the central tube comprises a substantially cylindrical outer surface with an upper opening, wherein the individual nanoparticles and nanofibers are propelled in a vortex around the outer surface of the central tube.
[0294] A fourteenth embodiment is any combination of the first thirteen embodiments, wherein a single nanoparticle is sucked into the upper opening of the central tube.
[0295] The 15th embodiment is any combination of the first 14 embodiments, wherein the inner cavity includes one or more outlets located at an end of the inner cavity opposite to the one or more inlets, and the system further includes an energy source coupled to the outlet, which is configured to apply negative pressure to the cavity to draw the nanofiber group out through the outlet.
[0296] A sixteenth embodiment is any combination of the preceding fifteen embodiments, further comprising a dispersing device fluidly coupled to the central tube outlet for dispersing individual nanoparticles.
[0297] A seventeenth embodiment is any combination of the previous sixteen embodiments, wherein the housing comprises a separator configured to mechanically separate large nanofiber clusters into nanofiber groups.
[0298] An eighteenth embodiment is any combination of the previous seventeen embodiments, further comprising a hopper for feeding large nanoparticle clusters to the separator at a specified rate.
[0299] A 19th embodiment is any combination of the previous 18 embodiments, wherein the separator comprises a housing and a plurality of rotatable blades mounted within the housing, wherein the blades are configured to mechanically separate large nanoparticle clusters into smaller nanoparticle clusters.
[0300] A twentieth embodiment is any combination of the preceding nineteen embodiments, wherein the plurality of blades comprises at least a first blade and a second blade, wherein the first blade has a different pitch and camber than the second blade.
[0301] The 21st embodiment is a fibrous material formed by any combination of the previous 20 embodiments.
[0302] The 22nd embodiment is a filter medium formed by any combination of the previous 20 embodiments.
Claims
1. A method for isolating a single nanoparticle in a gaseous medium, the method comprising: providing a group of nanofibers in a gaseous medium; and The group of nanofibers is pushed to a surface to separate at least a portion of the group of nanofibers into individual nanoparticles, wherein at least one dimension of the individual nanoparticles is less than 1 micron.
2. The method of claim 1, wherein the group of nanofibers is pushed to the surface at a speed of about 500 feet per minute (fpm) to about 10,000 fpm.
3. The method of claim 2, wherein the velocity is from about 2,000 fpm to about 6,000 fpm. The method according to claim 1 , wherein the gaseous medium is compressed air.
5. The method of claim 1, further comprising mechanically separating large nanoparticle clusters into the nanofiber groups.
6. The method of claim 1, further comprising applying negative pressure to the group of nanofibers to draw the nanofibers into an air flow.
7. The method of claim 6, further comprising applying negative pressure to the air flow to push the group of nanofibers toward the surface.
8. The method of claim 7, further comprising pushing the nanofiber through a channel into a joint, wherein the surface is located at the joint.
9. The method of claim 8, wherein the joint is a substantially T-shaped joint.
10. The method according to claim 7, further comprising: pushing the single nanoparticle and the group of nanofibers into the lumen of a reactor; and The individual nanoparticles are separated from the group of nanofibers in a reactor.
11. The method of claim 10, wherein the individual nanoparticles and the group of nanofibers are propelled into the inner cavity at a velocity vector that creates a vortex within the reactor.
12. The method of claim 11, wherein the lumen comprises a substantially central tube and the velocity vector comprises a direction transverse to a longitudinal axis of the tube.
13. The method of claim 13, wherein the direction is substantially tangential to the outer surface of the tube.
14. The method of claim 13, wherein the central tube comprises a substantially cylindrical outer surface having an upper opening, wherein the single nanoparticle and the group of nanofibers are propelled in a vortex around the outer surface of the central tube.
15. The method of claim 14, wherein the single nanoparticle is drawn into the upper opening of the central tube.
16. The method of claim 14, further comprising applying negative pressure to the cavity to aspirate the group of nanofibers from the cavity.
17. The method of claim 1, wherein the group of nanofibers comprises entangled chopped nanoparticles.
18. The method of claim 7, further comprising applying the negative pressure with an ejector.
19. The method of claim 5, further comprising feeding the large nanoparticle clusters to a separator at a specified rate.
20. The method of claim 15, further comprising drawing the single nanoparticle from a central tube of the lumen into a nozzle and dispersing the single nanoparticle into fibers to form a product.
21. The method of claim 20, wherein the product is a filter.
22. A system for isolating a single nanoparticle in a gaseous medium, the system comprising: a housing configured to house the group of nanofibers; a pump coupled to the housing; and a channel coupled to the pump and having a surface, The pump is configured to push the group of nanofibers toward a surface at a velocity sufficient to generate individual nanoparticles from at least a portion of the group of nanofibers.
23. The system of claim 22, wherein the velocity is from about 500 feet per minute (fpm) to about 10,000 fpm.
24. The system of claim 23, wherein the velocity is from about 2,000 fpm to about 6,000 fpm.
25. The system of claim 22, wherein the group of nanoparticles comprises entangled chopped nanoparticles.
26. The system of claim 22, wherein the channel comprises a joint, and wherein the surface is located at the joint.
27. The method of claim 26, wherein the joint is a substantially T-shaped joint.
28. The system of claim 22, further comprising: A source of compressed air; and The source of compressed air is coupled to the second channel of the pump.
29. The system of claim 28, wherein the pump comprises an ejector configured to generate negative pressure to draw the group of nanofibers out of the housing and through the first channel.
30. The system of claim 29, further comprising: a reactor having an interior cavity coupled to the channel; The reactor is configured to separate the individual nanoparticles from the group of nanofibers.
31. The system of claim 30, wherein the interior cavity of the reactor comprises one or more inlets coupled to the channel, and wherein the pump is configured to propel the individual nanoparticles and nanofibers through the inlets at a velocity vector that creates a vortex within the reactor.
32. The system of claim 31 , wherein the lumen comprises a substantially central tube and the velocity vector comprises a direction transverse to a longitudinal axis of the tube.
33. The system of claim 32, wherein the direction is substantially tangential to an outer surface of the tube.
34. The system of claim 32, wherein the central tube comprises a substantially cylindrical outer surface having an upper opening, wherein the individual nanoparticles and nanofibers are propelled in a vortex around the outer surface of the central tube.
35. The system of claim 34, wherein the single nanoparticle is drawn into the upper opening of the central tube.
36. A system according to claim 35, wherein the inner cavity includes one or more outlets located at an end of the inner cavity opposite to the one or more inlets, and the system further includes an energy source coupled to the outlet, which is configured to apply negative pressure to the cavity to suck the nanofiber group out through the outlet.
37. The system of claim 35, further comprising a dispersion device fluidly coupled to the central tube outlet for dispersing the individual nanoparticles.
38. The system of claim 22, wherein the housing comprises a separator configured to mechanically separate the large nanofiber clusters into the nanofiber groups.
39. The system of claim 38, further comprising a hopper for feeding the large nanoparticle clusters to the separator at a specified rate.
40. The system of claim 39, wherein the separator comprises a housing and a plurality of rotatable blades mounted within the housing, wherein the blades are configured to mechanically separate the large nanoparticle clusters into smaller nanoparticle clusters.
41. The system of claim 40, wherein the plurality of blades comprises at least a first blade and a second blade, wherein the first blade has a different pitch and camber than the second blade.
42. A fibrous material formed by the method of claim 1.
43. A filter medium formed by the method of claim 1.
Citation Information
Patent Citations
Multilayer filter medium for filter, method for producing the same, and air filter
US10252201B2
Durable nanofiber synthetic filter media
US10799820B2
Integrated nanofiber filter media
US20090266759A1
Wind turbine
US20200040941A1
Multi-die melt blowing system for forming co-mingled structures and method thereof
US20200216979A1